Adhesive sheet
The adhesive sheet with a high glass transition temperature and carbon-carbon double bond ensures easy separation and residue-free removal from adherends, addressing the issue of adhesive residue and damage from high-temperature exposure.
Patent Information
- Application Number
- JP2020571147
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-02-06
- Filing Date
- 2020-01-30
- Publication Date
- 2025-01-06
- Estimated Expiration
- 2040-01-30
AI Technical Summary
Conventional pressure-sensitive adhesives fail to achieve satisfactory separation and removability from adherends after exposure to high temperatures, leading to adhesive residue and potential damage to the adherend due to insufficient heat resistance.
A pressure-sensitive adhesive sheet with a polymer having a glass transition temperature of -63°C or higher and an adhesive force reduction rate of 17% or more, featuring a carbon-carbon double bond that reacts to reduce adhesive strength upon curing, ensuring easy separation and preventing residue even at high temperatures.
The adhesive sheet effectively separates from adherends with minimal residue and load, preventing damage by maintaining adhesion and reducing adhesive strength post-curing, even under high-temperature conditions.
Smart Images

Figure 0007608169000003 
Figure 0007608169000004 
Figure 0007608169000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a pressure-sensitive adhesive sheet. This application claims priority based on Japanese Patent Application No. 2019-019830, filed on February 6, 2019, the entire contents of which are incorporated herein by reference. [Background technology]
[0002] Generally, adhesives (also called pressure-sensitive adhesives; the same applies below) are in a soft solid (viscoelastic) state in a temperature range around room temperature, and have the property of easily adhering to an adherend by pressure. Adhesives are widely used in various fields in the form of a supported adhesive sheet having an adhesive layer on a support, or in the form of a support-less adhesive sheet having no support, because of the ease of application to the adherend. Such adhesives can be exposed to temperature changes, such as heating, while attached to the adherend. In addition, they can be removed from the adherend after their adhesive purpose has been completed. Patent documents 1 and 2 are prior art documents that disclose this type of conventional technology. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Japanese Patent Application Publication No. 2015-120884 [Patent Document 2] Japanese Patent Application Publication No. 2018-12751 Summary of the Invention [Problem to be solved by the invention]
[0004] The adhesive is being considered for use in a number of applications in which it is attached to an adherend, exposed to high temperature conditions, and then separated from the adherend. A specific example is a use in which a number of miniaturized semiconductor chips (such as LED chips) are fixed on the adhesive surface of a single adhesive sheet, the semiconductor chips are processed on the adhesive sheet by sealing with a resin such as epoxy resin, and the semiconductor chips are separated from the adhesive sheet after the processing is completed. In this use, high temperature heating is performed during resin sealing, so heat resistance is required so that the ease of peeling is not impaired even after heating. In the case of fixing chips on a printed wiring board (PCB), heating may be performed during wire bonding and resin sealing, so that adhesives having heat resistance can be expected to be used in the same way as in the case of semiconductor chip processing. In addition, in the printing of solder paste on a thin wafer, an adhesive sheet that can withstand the heat of the solder reflow process can be expected to be used as a support tape for the thin wafer.
[0005] However, conventional adhesives have not been able to achieve satisfactory separation and removal properties from the adherend after the above-mentioned high-temperature heating. For example, ultraviolet (UV) curing adhesives are known as known adhesives that are removed from the adherend after completing their bonding purpose. UV curing adhesives can be irradiated with UV at an appropriate timing before removal to reduce the adhesive strength, and can be successfully removed from the adherend. However, when the above-mentioned UV curing adhesive is exposed to a high temperature state of a predetermined temperature or higher after bonding, the adhesive strength does not decrease even if UV is irradiated thereafter, and there is a problem that adhesive residue occurs when the adhesive is removed from the adherend. In addition, in an embodiment in which the adhesive strength does not decrease, when the adherend contains a resin such as a sealing resin, a load is applied to the adherend when it is separated and removed (peeled off) from the adherend after heating, and defects such as cracks, chips, and breaks may occur in the adherend.
[0006] Regarding the separation and removal from the adherend after heating, for example, Patent Document 2 proposes an adhesive that can be attached to an adherend, heated, and then irradiated with active energy rays such as UV to be peeled off from the adherend without leaving any adhesive residue. However, the design concept of the adhesive proposed in Patent Document 2 is to limit adhesion to the uneven surface of the adherend to a certain extent in the initial stage before UV irradiation (before curing) to improve the peelability and prevention of adhesive residue after curing, and there is a limit to achieving compatibility with the improvement of initial adhesive strength. Furthermore, as a result of the investigation, it was found that there is room for improvement in the prevention of adhesive residue depending on the heating temperature during use. If an adhesive that has good separation (peeling) when separated from an adherend and can prevent adhesive residue even in a use mode where it is exposed to high temperatures such as resin sealing is realized, it would be practically meaningful.
[0007] The present invention has been created in consideration of the above circumstances, and aims to provide an adhesive sheet that can be easily separated from an adherend after curing treatment, even when exposed to high temperatures, and that can prevent adhesive residue upon separation. [Means for solving the problem]
[0008] According to the present specification, there is provided a pressure-sensitive adhesive sheet having a pressure-sensitive adhesive layer. The glass transition temperature of the polymer contained in the pressure-sensitive adhesive layer of this pressure-sensitive adhesive sheet is -63°C or higher. Furthermore, the pressure-sensitive adhesive sheet has an adhesive strength reduction rate of 17% or higher, calculated by the following formula: Adhesive force reduction rate (%)=(1-B / A)×100 In the above formula, A is the initial 180-degree peel strength ([N / 20 mm]) against a stainless steel plate. B is the initial peel strength ([N / 20 mm]) against a stainless steel plate, heated at 180°C for 1 hour, left at 25°C for 30 minutes, and measured with an illuminance of 60 mW / cm 2 This is the 180-degree peel strength ([N / 20 mm]) after heat-hardening treatment on a stainless steel plate, measured after exposure to ultraviolet light at 300 K.
[0009] The pressure-sensitive adhesive sheet can be attached to an adherend with a predetermined or higher adhesive strength before the curing process. In addition, the glass transition temperature (Tg) of the polymer contained in the pressure-sensitive adhesive layer is −63° C. or higher, and the adhesive strength reduction rate after the heating-curing process is 17% or higher. Therefore, even if the pressure-sensitive adhesive sheet is exposed to high temperatures, it can be easily separated from the adherend after the curing process, and adhesive residue can be prevented. For example, when the adherend contains a resin such as a sealing resin, it can be easily separated from the adherend with a small load on the resin, so that damage to the adherend when the pressure-sensitive adhesive sheet is removed can be prevented or reduced.
[0010] Some preferred embodiments of the pressure-sensitive adhesive sheet have an initial 180-degree peel strength against a stainless steel plate of more than 1.0 N / 20 mm. Pressure-sensitive adhesive sheets having such initial adhesive strength can adhere well to an adherend before a curing treatment.
[0011] The adhesive sheet according to some preferred embodiments has the following characteristics: an illuminance of 60 mW / cm after heating at 180° C. for 1 hour and leaving at 25° C. for 30 minutes 2 and after a heat-curing treatment in which ultraviolet light is irradiated at 3000 K, the modulus of elasticity of the pressure-sensitive adhesive layer measured by nanoindentation is 22 MPa or more. A pressure-sensitive adhesive layer that satisfies the above characteristics has a predetermined softness before the curing treatment and can adhere well to an adherend, and the pressure-sensitive adhesive layer is cured by the heat-curing treatment to have a modulus of elasticity (modulus of elasticity measured by nanoindentation) of 22 MPa or more, so that even when exposed to high temperatures, adhesive residue can be highly prevented when the pressure-sensitive adhesive layer is separated from the adherend.
[0012] The elastic modulus of the adhesive layer can typically be measured by a nanoindentation method. In addition, the terms "adhesive sheet" and "adhesive layer" in this specification refer to the "adhesive sheet" and "adhesive layer" before the heat-curing treatment, respectively, unless otherwise specified.
[0013] In some preferred embodiments, the pressure-sensitive adhesive layer contains a carbon-carbon double bond. In the pressure-sensitive adhesive layer containing a carbon-carbon double bond, the carbon-carbon double bond present therein reacts and hardens by a predetermined curing treatment, and the adhesive strength decreases. Therefore, even when exposed to high temperatures, the pressure-sensitive adhesive layer is easily separated from the adherend, and adhesive residue can be preferably prevented when the pressure-sensitive adhesive layer is separated from the adherend.
[0014] In some preferred embodiments, the polymer includes a polymer having a carbon-carbon double bond. More preferably, the polymer is an acrylic polymer. In a typical embodiment, the acrylic polymer is a polymer of a monomer component including an alkyl (meth)acrylate. By configuring as described above, the effect of the technology disclosed herein is preferably realized.
[0015] In some preferred embodiments, the alkyl (meth)acrylate includes an alkyl (meth)acrylate A1 having 9 or less carbon atoms in the alkyl group. Such a configuration in which the length of the side chain alkyl group is limited tends to provide high cohesive strength capable of preventing adhesive residue, and also tends to provide excellent adhesive strength to polar adherends such as metals. The alkyl (meth)acrylate A1 preferably includes an alkyl (meth)acrylate having 7 or less carbon atoms in the alkyl group. The content of the alkyl (meth)acrylate A1 in the monomer component is preferably 20% by weight or more.
[0016] In some embodiments, the alkyl (meth)acrylate may contain an alkyl (meth)acrylate A2 having an alkyl group with 7 or more carbon atoms as the alkyl (meth)acrylate A1 or as a monomer different from the alkyl (meth)acrylate A1. By using the alkyl (meth)acrylate A2, for example, the adhesive strength after curing treatment is easily reduced, and better adherend separation properties and adhesive residue prevention properties are easily obtained.
[0017] In some embodiments, the pressure-sensitive adhesive sheet further comprises a base layer. The pressure-sensitive adhesive layer is provided on at least one surface of the base layer. The pressure-sensitive adhesive sheet comprising the base layer has a predetermined rigidity, and therefore can be excellent in processability and handling. The pressure-sensitive adhesive sheet according to some embodiments is a single-sided adhesive sheet in which the pressure-sensitive adhesive layer is provided on one surface of the base layer. The pressure-sensitive adhesive sheet according to some other embodiments is a double-sided adhesive sheet in which the pressure-sensitive adhesive layer is provided on both surfaces of the base layer. The pressure-sensitive adhesive sheet according to still other embodiments is a double-sided adhesive sheet in which a first pressure-sensitive adhesive layer is provided as the pressure-sensitive adhesive layer on one surface of the base layer, and a second pressure-sensitive adhesive layer different from the first pressure-sensitive adhesive layer is provided on the other surface of the base layer. Alternatively, the technology disclosed herein can also be preferably implemented in an embodiment in which the base layer is a substrateless double-sided adhesive sheet substantially composed only of the pressure-sensitive adhesive layer. [Brief description of the drawings]
[0018] [Figure 1] FIG. 2 is a cross-sectional view showing a schematic configuration example of a pressure-sensitive adhesive sheet. [Diagram 2] FIG. 4 is a cross-sectional view that illustrates a schematic configuration example of the pressure-sensitive adhesive sheet. [Diagram 3] FIG. 4 is a cross-sectional view that illustrates a schematic configuration example of the pressure-sensitive adhesive sheet. [Figure 4] FIG. 4 is a cross-sectional view that illustrates a schematic configuration example of the pressure-sensitive adhesive sheet. [Diagram 5] FIG. 4 is a cross-sectional view that illustrates a schematic configuration example of the pressure-sensitive adhesive sheet. [Figure 6] FIG. 4 is a cross-sectional view that illustrates a schematic configuration example of the pressure-sensitive adhesive sheet. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] Preferred embodiments of the present invention will be described below. Note that matters other than those specifically mentioned in this specification that are necessary for carrying out the present invention can be understood as design matters for a person skilled in the art based on the prior art in the relevant field. The present invention can be carried out based on the contents disclosed in this specification and the technical common sense in the relevant field. In the following drawings, components and parts having the same function may be denoted by the same reference numerals, and duplicated descriptions may be omitted or simplified. In addition, the embodiments shown in the drawings are schematic in order to clearly explain the present invention, and do not necessarily accurately represent the size or scale of the PSA sheet actually provided as a product.
[0020] <Composition of adhesive sheet> The adhesive sheet disclosed herein comprises an adhesive layer. This adhesive layer typically constitutes at least one surface of the adhesive sheet. The adhesive sheet may be an adhesive sheet with a substrate in a form having an adhesive layer on one or both sides of a substrate (support), or may be an adhesive sheet without a substrate in a form in which the adhesive layer is held by a release liner (which may also be understood as a substrate having a release surface). In this case, the adhesive sheet may be composed of only an adhesive layer. The concept of an adhesive sheet as used herein may include those called adhesive tapes, adhesive labels, adhesive films, etc. In addition, the adhesive layer is typically formed continuously, but is not limited to such a form, and may be an adhesive layer formed in a regular or random pattern such as a dotted or striped pattern. In addition, the adhesive sheet provided by the present specification may be in the form of a roll or a sheet. Alternatively, it may be an adhesive sheet in the form of a further processed into various shapes.
[0021] The adhesive sheet disclosed herein may have a cross-sectional structure, for example, as shown in Fig. 1 to Fig. 6. Among these, Fig. 1 and Fig. 2 are structural examples of a one-sided adhesive substrate-attached adhesive sheet. The adhesive sheet 1 shown in Fig. 1 has a structure in which an adhesive layer 21 is provided on one side 10A (non-releasable) of a base layer 10, and a surface (adhesive surface) 21A of the adhesive layer 21 is protected by a release liner 31, at least the adhesive layer side of which is a release surface. The adhesive sheet 2 shown in Fig. 2 has a structure in which an adhesive layer 21 is provided on one side 10A (non-releasable) of a base layer 10. In this adhesive sheet 2, the other side 10B of the base layer 10 is a release surface, and when the adhesive sheet 2 is rolled up, the adhesive layer 21 comes into contact with the other side 10B, and the surface (adhesive surface) 21B of the adhesive layer is protected by the other side 10B of the base layer 10.
[0022] 3 and 4 are configuration examples of a double-sided adhesive type substrate-attached pressure-sensitive adhesive sheet. The pressure-sensitive adhesive sheet 3 shown in FIG. 3 has pressure-sensitive adhesive layers 21 and 22 provided on each side (both non-removable) of a substrate layer 10, and these pressure-sensitive adhesive layers are protected by release liners 31 and 32, at least the pressure-sensitive adhesive layer side being a release surface. The pressure-sensitive adhesive sheet 4 shown in FIG. 4 has pressure-sensitive adhesive layers 21 and 22 provided on each side (both non-removable) of a substrate layer 10, and one of these pressure-sensitive adhesive layers 21 is protected by a release liner 31, both of which are release surfaces. The pressure-sensitive adhesive sheet 4 can be configured such that the pressure-sensitive adhesive layer 22 is also protected by the release liner 31 by rolling the pressure-sensitive adhesive sheet 4 and abutting the other pressure-sensitive adhesive layer 22 against the back surface of the release liner 31. In addition, in the adhesive sheets 3 and 4 shown in Figures 3 and 4, both of the adhesive layers 21 and 22 may be adhesive layers disclosed herein (described in detail later), or only one of the adhesive layers (e.g., adhesive layer 21) may be an adhesive layer disclosed herein and the other adhesive layer (e.g., adhesive layer 22) may be an adhesive layer different from the adhesive layer disclosed herein (e.g., a conventionally known adhesive layer).
[0023] 5 and 6 are configuration examples of a substrate-less double-sided adhesive pressure-sensitive adhesive sheet. The pressure-sensitive adhesive sheet 5 shown in FIG. 5 has a configuration in which both sides 21A and 21B of a substrate-less adhesive layer 21 are protected by release liners 31 and 32, at least the adhesive layer side being a release surface. The pressure-sensitive adhesive sheet 6 shown in FIG. 6 has a configuration in which one surface (adhesive surface) 21A of the substrate-less adhesive layer 21 is protected by a release liner 31, both sides of which are release surfaces, and when this is rolled up, the other surface (adhesive surface) 21B of the adhesive layer 21 abuts against the back surface of the release liner 31, so that the other surface 21B is also protected by the release liner 31.
[0024] <Characteristics of adhesive sheet> The initial adhesive strength of the adhesive sheet disclosed herein is not limited to a specific range, since it can be set according to the mode of use or purpose. In some preferred embodiments, the adhesive sheet can have an initial 180° peel strength (initial adhesive strength) against a stainless steel plate measured under conditions of a peel angle of 180° and a speed of 300 mm / min in an environment of 23°C based on JIS Z 0237:2000 of about 1 N / 20 mm or more (typically more than 1.0 N / 20 mm). An adhesive sheet exhibiting an initial adhesive strength of a predetermined value or more can be well adhered to an adherend. From such a viewpoint, the initial adhesive strength is suitably about 2 N / 20 mm or more, preferably about 3 N / 20 mm or more, more preferably about 5 N / 20 mm or more (for example, about 7 N / 20 mm or more, typically about 9 N / 20 mm or more). The upper limit of the initial adhesive strength is not particularly limited, and may be less than 30 N / 20 mm, or may be less than 20 N / 20 mm (for example, less than 15 N / 20 mm). The initial adhesive strength is a peel strength measured before a curing treatment, specifically, by the method described in the Examples below.
[0025] In addition, the adhesive strength of the adhesive sheet disclosed herein after the curing treatment can be set within a range that satisfies the adhesive strength reduction rate described below, and is not limited to a specific range. In some preferred embodiments, the adhesive sheet is prepared by attaching the adhesive layer to a stainless steel plate and subjecting it to a heat-curing treatment (heating at 180°C for 1 hour, leaving it at 25°C for 30 minutes, and illuminance of 60 mW / cm2). 2 The 180 degree peel strength after curing treatment (adhesive strength after heat-curing treatment) measured after performing a treatment in which the adhesive strength after heat-curing treatment is limited can be about 3 N / 20 mm or less. An adhesive sheet with limited adhesive strength after heat-curing treatment is easy to separate from an adherend, and adhesive residue tends to be preferably prevented. From this viewpoint, the adhesive strength after heat-curing treatment is suitably about 2 N / 20 mm or less, and preferably about 1 N / 20 mm or less (e.g., 0.7 N / 20 mm or less, typically 0.5 N / 20 mm or less). The lower limit of the adhesive strength after heat-curing treatment can be, for example, about 0.1 N / 20 mm or more. The adhesive strength after heat-curing treatment is specifically measured by the method described in the Examples below.
[0026] In some exemplary embodiments, the pressure-sensitive adhesive sheet disclosed herein comprises a compound represented by the formula: Adhesive force reduction rate (%)=(1-B / A)×100 (In the above formula, A is the initial 180° peel strength against a stainless steel plate ([N / 20 mm]), and B is the 180° peel strength against a stainless steel plate after heat-curing treatment ([N / 20 mm]).); It is characterized by an adhesive strength reduction rate of 17% or more obtained by the above formula. An adhesive sheet showing an adhesive strength reduction rate of a predetermined value or more can be adhered to an adherend before curing treatment, and even if exposed to high temperatures, after curing treatment, it is easy to separate from the adherend due to the reduced adhesive strength, and adhesive residue can be prevented. For example, in the manufacture of a circuit board, in an embodiment in which a chip is placed on an adhesive sheet and an encapsulating resin is further cured thereon, after heating to cure the encapsulating resin, not only can the chip be easily separated from the electrodes (metal) on the surface of the chip, but also the encapsulating resin (cured resin) can be easily separated with little load on the encapsulating resin. Therefore, it is possible to prevent defects such as cracks, chips, and breaks in an adherend containing resin. In the technology disclosed herein, the separability from an adherend includes the above-mentioned separability (peelability).
[0027] The adhesive strength reduction rate is suitably more than 20%, and may be 35% or more (e.g., 50% or more). The adhesive strength reduction rate is preferably 65% or more, more preferably 75% or more, and even more preferably 85% or more (e.g., 90% or more). The upper limit of the adhesive strength increase rate may be approximately 99% or less (e.g., 95% or less). The adhesive sheet disclosed in this specification includes an embodiment in which there is no restriction on the adhesive strength reduction rate, and in such an embodiment, the adhesive sheet is not limited to one having the above characteristics.
[0028] (Elastic modulus after heat-curing treatment) The adhesive sheet disclosed herein has the following characteristics: after heating at 180°C for 1 hour and leaving at 25°C for 30 minutes, the illuminance is 60 mW / cm 2It is preferable that the adhesive layer has a modulus of elasticity of 22 MPa or more measured by the nanoindentation method after a heat-curing treatment in which ultraviolet light is irradiated at 1000 .0001. More specifically, the adhesive layer satisfying the above characteristics is formed by an adhesive layer forming treatment such as drying, but is in a state before the heat-curing treatment, and is configured such that the modulus of elasticity measured by the nanoindentation method after the heat-curing treatment is 22 MPa or more in that state. By satisfying the above characteristics, the adhesive layer has a predetermined softness before the curing treatment and can be well adhered to the adherend with a predetermined or higher adhesive force. In addition, the adhesive layer satisfying the above characteristics is designed to have a predetermined or higher modulus of elasticity by the heat-curing treatment, so that even when exposed to high temperatures, adhesive residue can be highly prevented when separated from the adherend.
[0029] The adhesive layer disclosed herein is configured to have an elastic modulus of about 30 MPa or more (e.g., about 50 MPa or more) after the above-mentioned heat-curing treatment, preferably about 70 MPa or more, more preferably about 90 MPa or more, even more preferably about 100 MPa or more, and particularly preferably about 120 MPa or more (typically about 140 MPa or more, for example, about 160 MPa or more) in terms of preventing adhesive residue and reducing adhesive strength after curing treatment. The upper limit of the elastic modulus of the adhesive layer after the above-mentioned heat-curing treatment is not particularly limited, and may be about 500 MPa or less, or may be about 300 MPa or less.
[0030] The elastic modulus of the pressure-sensitive adhesive layer after the heat-curing treatment is measured by a nanoindentation method, the specific measurement method being as described in the Examples below.
[0031] The adhesive sheet disclosed herein may be one in which the size of the adhesive component (adhesive residue) remaining on the adherend is 10 μm or more and less than 100 μm in an adhesive residue evaluation carried out by the method described in the Examples below. Preferably, the size of the adhesive residue is less than 10 μm, or no adhesive residue is observed. An adhesive sheet that satisfies this characteristic can prevent adhesive residue when separated from the adherend after curing treatment, even when exposed to high temperatures.
[0032] <Adhesive layer> The adhesive layer disclosed herein is preferably a material that exhibits a soft solid (viscoelastic) state in a temperature range around room temperature and has the property of easily adhering to an adherend by pressure. The adhesive referred to here is generally a material having a complex tensile modulus E * (1Hz)<10 7 dyne / cm 2 The material may be a material having the properties satisfying the above (typically, a material having the above properties at 25°C).
[0033] (polymer) The glass transition temperature (Tg) of the polymer (typically the base polymer) contained in the adhesive layer disclosed herein is -63°C or higher. This allows the adhesive to have a certain level of cohesiveness, and can prevent adhesive residue when separated and removed from the adherend after curing treatment. The Tg of the polymer is suitably -60°C or higher from the viewpoint of preventing adhesive residue, preferably -55°C or higher, more preferably -50°C or higher, and may be -40°C or higher, -30°C or higher, -20°C or higher, or -15°C or higher. The upper limit of the Tg of the polymer in the adhesive layer is not particularly limited, and is suitably 15°C or lower from the viewpoint of adhesion to the adherend, and may be, for example, 5°C or lower. From the viewpoint of improving adhesion to the adherend and exhibiting good retention, the Tg is preferably 0°C or lower, more preferably -5°C or lower. In some embodiments, the Tg of the polymer may be -10°C or lower, -15°C or lower, -20°C or lower, or -30°C or lower.
[0034] In this specification, the Tg of a polymer refers to the glass transition temperature calculated by the Fox formula based on the composition of the monomer raw material constituting the polymer, more specifically, the glass transition temperature calculated by the Fox formula based on the composition of the monomer raw material constituting the main chain of the polymer. The Fox formula is a relational expression between the Tg of a copolymer and the glass transition temperature Tgi of a homopolymer obtained by homopolymerizing each of the monomers constituting the copolymer, as shown below. 1 / Tg=Σ(Wi / Tgi) In the above Fox formula, Tg represents the glass transition temperature (unit: K) of the copolymer, Wi represents the weight fraction of monomer i in the copolymer (copolymerization ratio on a weight basis), and Tgi represents the glass transition temperature (unit: K) of the homopolymer of monomer i.
[0035] The glass transition temperature of the homopolymer used to calculate Tg is a value described in a publicly known document. For example, for the monomers listed below, the following values are used as the glass transition temperatures of the homopolymers of the monomers. 2-Ethylhexyl acrylate -70℃ n-Butyl acrylate -55℃ Ethyl acrylate -22℃ Lauryl acrylate -3℃ N-Acryloylmorpholine 145℃ 2-Hydroxyethyl acrylate -15℃ 4-Hydroxybutyl acrylate -40℃
[0036] For the glass transition temperatures of homopolymers of monomers other than those listed above, the values given in "Polymer Handbook" (3rd Edition, John Wiley & Sons, Inc., 1989) shall be used. When multiple values are given in this document, the highest value shall be used.
[0037] For monomers for which the glass transition temperature of the homopolymer is not described in the Polymer Handbook, the value obtained by the following measurement method shall be used (see JP 2007-51271 A). Specifically, 100 parts by weight of monomer, 0.2 parts by weight of azobisisobutyronitrile, and 200 parts by weight of ethyl acetate as a polymerization solvent are charged into a reactor equipped with a thermometer, a stirrer, a nitrogen inlet tube, and a reflux condenser, and stirred for 1 hour while passing nitrogen gas through. After removing oxygen from the polymerization system in this way, the temperature is raised to 63°C and reacted for 10 hours. Then, the mixture is cooled to room temperature to obtain a homopolymer solution with a solid concentration of 33% by weight. Then, the homopolymer solution is cast and applied onto a release liner, and dried to prepare a test sample (sheet-shaped homopolymer) with a thickness of about 2 mm. This test sample was punched out into a disk with a diameter of 7.9 mm, sandwiched between parallel plates, and subjected to a shear strain of 1 Hz using a viscoelasticity tester (ARES, Rheometrics Corporation). Viscoelasticity was measured in shear mode at a temperature range of -70 to 150°C and a heating rate of 5°C / min. The peak top temperature of tan δ was taken as the Tg of the homopolymer.
[0038] The polymer (typically the base polymer) contained in the adhesive layer disclosed herein can be selected from among those that have a predetermined Tg and can realize a predetermined adhesive strength reduction rate, and is not limited to a specific type. The above-mentioned polymer can be, for example, one or more of various polymers such as acrylic polymers, rubber polymers (e.g., natural rubber, chloroprene rubber, styrene-butadiene rubber, nitrile rubber, etc.), polyester, urethane polymers, polyether, silicone polymers, polyamide, fluorine-based polymers, ethylene-vinyl acetate polymers, epoxy resins, vinyl chloride polymers, cyanoacrylate polymers, cellulose polymers (nitrocellulose polymers, etc.), phenolic resins, polyimides, polyolefins, styrene polymers, polyvinyl acetate, polyvinyl alcohol, polyvinyl acetal, polyvinyl pyrrolidone, polyvinyl butyral, polybenzimidazole, melamine resins, urea resins, and resorcinol polymers. From the viewpoints of adhesion, cost, and the like, acrylic polymers, rubber polymers, polyesters, urethane polymers, polyethers, silicone polymers, polyamides, and fluorine-based polymers are preferred, acrylic polymers and rubber polymers are more preferred, and acrylic polymers are particularly preferred. The "base polymer" of the adhesive layer refers to the main component of the polymer contained in the adhesive layer, and is not to be construed in any other limiting sense. The polymer is preferably a rubber-like polymer that exhibits rubber elasticity in a temperature range around room temperature. In this specification, the "main component" refers to a component contained in an amount of more than 50% by weight, unless otherwise specified.
[0039] The acrylic polymer is preferably, for example, a polymer of a monomer raw material that contains an alkyl (meth)acrylate as a main monomer and may further contain a sub-monomer copolymerizable with the main monomer, where the main monomer refers to a component that accounts for more than 50% by weight of the monomer composition in the monomer raw material. The term "acrylic polymer" refers to a polymer containing, as a monomer unit constituting the polymer, a monomer unit derived from a monomer having at least one (meth)acryloyl group in one molecule. Hereinafter, a monomer having at least one (meth)acryloyl group in one molecule is also referred to as an "acrylic monomer". In this specification, an acrylic polymer is defined as a polymer containing a monomer unit derived from an acrylic monomer. A typical example of such an acrylic polymer is an acrylic polymer in which the proportion of the acrylic monomer in the monomer composition of the acrylic polymer is more than 50% by weight. In addition, the term "(meth)acryloyl" refers collectively to acryloyl and methacryloyl. Similarly, the term "(meth)acrylate" refers collectively to acrylate and methacrylate, and the term "(meth)acrylic" refers collectively to acrylic and methacrylic.
[0040] As the alkyl(meth)acrylate, for example, a compound represented by the following formula (A) can be suitably used. CH 2 =C(R 1 )COOR 2 (A) Here, R in the above formula (A) 1 is a hydrogen atom or a methyl group. 2 is a chain alkyl group having 1 to 20 carbon atoms (hereinafter, this range of carbon atoms is referred to as "C 1-20 From the viewpoint of the storage modulus of the adhesive layer, R 2 C 1-14 (For example, C 1-12 ), alkyl (meth)acrylates having a chain alkyl group of R 1 is a hydrogen atom and R 2 C 1-20 (For example, C 1-14 , typically C 1-12 ) alkyl acrylate, which is a chain alkyl group, is more preferred.
[0041] R 2 C 1-20Examples of alkyl(meth)acrylates, which are chain alkyl groups, include methyl(meth)acrylate, ethyl(meth)acrylate, propyl(meth)acrylate, isopropyl(meth)acrylate, n-butyl(meth)acrylate, isobutyl(meth)acrylate, s-butyl(meth)acrylate, pentyl(meth)acrylate, isopentyl(meth)acrylate, hexyl(meth)acrylate, heptyl(meth)acrylate, 2-ethylhexyl(meth)acrylate, octyl(meth)acrylate, and isooctyl(meth)acrylate. Examples of the alkyl (meth)acrylate include ethyl acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, nonadecyl (meth)acrylate, and eicosyl (meth)acrylate. These alkyl (meth)acrylates can be used alone or in combination of two or more. Examples of preferred alkyl (meth)acrylates include ethyl acrylate (EA), n-butyl acrylate (BA), 2-ethylhexyl acrylate (2EHA), and lauryl acrylate (LA).
[0042] In some preferred embodiments, the alkyl (meth)acrylate is an alkyl (meth)acrylate A1 (i.e., R 2 C 1-9The monomer includes an alkyl (meth)acrylate, which is an alkyl group of the side chain. In this way, the structure in which the length of the side chain alkyl group is limited tends to provide high cohesive strength that can prevent adhesive residue. For example, in a structure in which the polymer has a carbon-carbon double bond in its side chain (typically at the side chain end), the reaction of the carbon-carbon double bond can proceed smoothly during the curing process because the length of the side chain alkyl group is limited. In addition, because the length of the side chain alkyl group is limited, a pressure-sensitive adhesive containing a polymer obtained by polymerizing the monomer is likely to exhibit excellent adhesive strength to polar adherends such as metals.
[0043] The proportion of alkyl (meth)acrylate A1 in the total monomer components is suitably about 10% by weight or more, and from the viewpoint of favorably expressing the action of alkyl (meth)acrylate A1, it is preferably about 20% by weight or more, more preferably about 40% by weight or more, even more preferably about 55% by weight or more, particularly preferably about 65% by weight or more, for example, it may be about 75% by weight or more, it may be about 80% by weight or more, it may be about 85% by weight or more, it may be about 90% by weight or more, or it may be about 95% by weight or more. The upper limit of the proportion of alkyl (meth)acrylate A1 in the total monomer components is not particularly limited, and it is suitable to be 99.5% by weight or less (for example, 99% by weight or less), and in an embodiment in which a reactive group for curing treatment or a functional group that becomes a crosslinking point is introduced into the polymer, it is preferably about 95% by weight or less, more preferably about 90% by weight or less, even more preferably about 85% by weight or less (for example, about 75% by weight or less).
[0044] The content of the alkyl (meth)acrylate A1 in the total alkyl (meth)acrylate as the main monomer is suitably about 50% by weight or more, and from the viewpoint of preferably exerting the action of the alkyl (meth)acrylate A1, it is preferably about 70% by weight or more, more preferably about 80% by weight or more, even more preferably about 90% by weight or more, particularly preferably about 95% by weight or more, and may be, for example, about 99 to 100% by weight.
[0045] In some preferred embodiments, the alkyl (meth)acrylate A1 includes an alkyl (meth)acrylate A3 having an alkyl group with less than 8 carbon atoms. A pressure-sensitive adhesive including a polymer obtained by polymerizing a monomer component including this alkyl (meth)acrylate A3 is likely to exhibit excellent adhesive strength to polar adherends such as metals, and the reaction by curing treatment can proceed favorably. From this viewpoint, the number of carbon atoms in the alkyl group in the alkyl (meth)acrylate A3 is suitably 7 or less (typically less than 7), preferably 6 or less, more preferably 4 or less, and even more preferably 2 or less. From the viewpoint of adhesion to the adherend, the number of carbon atoms in the alkyl group in the alkyl (meth)acrylate A3 is preferably 2 or more.
[0046] In some embodiments, the alkyl(meth)acrylate A3 is an alkyl(meth)acrylate (C 4-7 Alkyl (meth)acrylate) and alkyl (meth)acrylate (C 1-3 alkyl (meth)acrylate). 4-7 The number of carbon atoms in the alkyl group of the alkyl (meth)acrylate is preferably 4 to 6 (for example, 4). 4-7 The alkyl (meth)acrylate is preferably an alkyl acrylate. 1-3 The number of carbon atoms in the alkyl group of the alkyl (meth)acrylate is preferably 1 or 2 (e.g., 2). 1-3 The alkyl (meth)acrylate is preferably an alkyl acrylate.
[0047] The alkyl (meth)acrylate A3 is C 4-7 Alkyl (meth)acrylate and C 1-3 In an embodiment comprising an alkyl (meth)acrylate, 4-7 Alkyl (meth)acrylate and C 1-3 The ratio of alkyl (meth)acrylate is not particularly limited, and C 4-7Alkyl (meth)acrylate and C 1-3 The weight ratio of the alkyl (meth)acrylate may be 1:9 to 9:1, may be 2:8 to 8:2, may be 3:7 to 7:3, or may be 4:6 to 6:4. 4-7 The content of alkyl (meth)acrylate is C 1-3 It is preferable that the content of the alkyl (meth)acrylate is higher than that of the C 4-7 The content of alkyl (meth)acrylate is, by weight, C 1-3 The content ratio may be 1.1 times or more (for example, 1.2 times or more) the content ratio of the alkyl (meth)acrylate.
[0048] The proportion of the alkyl (meth)acrylate A3 in the total monomer components is suitably about 10% by weight or more, and from the viewpoint of favorably expressing the action of the alkyl (meth)acrylate A1, it is preferably about 20% by weight or more, more preferably about 30% by weight or more, even more preferably about 40% by weight or more, particularly preferably about 50% by weight or more, for example, it may be about 60% by weight or more, may be about 70% by weight or more, may be about 80% by weight or more, or may be about 90% by weight or more. The upper limit of the proportion of the alkyl (meth)acrylate A3 in the total monomer components is not particularly limited, and it is suitably 99% by weight or less (for example, 90% by weight or less), and in an embodiment in which a reactive group for curing treatment or a functional group that becomes a crosslinking point is introduced into the polymer, it is preferably about 80% by weight or less, more preferably about 70% by weight or less, and even more preferably about 60% by weight or less.
[0049] The content of the alkyl (meth)acrylate A3 in the total alkyl (meth)acrylate as the main monomer is suitably approximately 5% by weight or more, and from the viewpoint of favorably exerting the action of the alkyl (meth)acrylate A3, it is preferably approximately 20% by weight or more, more preferably approximately 35% by weight or more, even more preferably approximately 45% by weight or more, and particularly preferably approximately 55% by weight or more, and may be, for example, approximately 65% by weight or more, approximately 75% by weight or more, or may be approximately 85% by weight or more (for example, approximately 90% by weight or more). The upper limit of the content of the alkyl (meth)acrylate A3 in the entire alkyl (meth)acrylate is 100% by weight, and is suitably, for example, approximately 95% by weight or less. From the viewpoint of preferably exerting the action of the alkyl (meth)acrylate A2 described below when it is contained, the upper limit is preferably approximately 90% by weight or less, more preferably approximately 85% by weight or less, and may be, for example, approximately 75% by weight or less, approximately 60% by weight or less, approximately 45% by weight or less, approximately 30% by weight or less, or approximately 15% by weight or less.
[0050] In some embodiments, the alkyl (meth)acrylate includes an alkyl (meth)acrylate A2 having 7 or more carbon atoms in the alkyl group as the alkyl (meth)acrylate A1 or A3, or as a monomer different from the alkyl (meth)acrylate A1 or A3. By using the alkyl (meth)acrylate A2, for example, the adhesive strength after curing treatment is easily reduced, and better adherend separation property and adhesive residue prevention property are easily obtained. The number of carbon atoms in the alkyl group in the alkyl (meth)acrylate A2 is preferably 8 or more, for example, 9 or more. From the viewpoint of adhesive properties such as adhesive strength, the number of carbon atoms in the alkyl group in the alkyl (meth)acrylate A2 is preferably 14 or less, more preferably 12 or less, and even more preferably 10 or less (typically 9 or less).
[0051] The content of the alkyl (meth)acrylate A2 in the total alkyl (meth)acrylate as the main monomer is suitably approximately 1% by weight or more, and from the viewpoint of favorably exerting the action of the alkyl (meth)acrylate A2, it is preferably approximately 5% by weight or more, more preferably approximately 15% by weight or more, even more preferably approximately 25% by weight or more, and particularly preferably approximately 35% by weight or more, for example, it may be approximately 45% by weight or more, may be approximately 60% by weight or more, or may be approximately 80% by weight or more (for example, approximately 90% by weight or more). The upper limit of the content of the alkyl (meth)acrylate A2 in the entire alkyl (meth)acrylate is 100% by weight, and is suitably, for example, approximately 90% by weight or less. From the viewpoint of preferably exerting the action of the alkyl (meth)acrylate A3 when it is contained, it is preferably approximately 70% by weight or less, more preferably approximately 60% by weight or less, and may be, for example, approximately 45% by weight or less, approximately 30% by weight or less, approximately 20% by weight or less, approximately 10% by weight or less, or approximately 5% by weight or less.
[0052] The blending ratio of the main monomer in the total monomer components is preferably about 55% by weight or more, and more preferably about 60% by weight or more (e.g., about 65% by weight or more). The upper limit of the blending ratio of the main monomer is not particularly limited, but is suitably 99.5% by weight or less (e.g., 99% by weight or less), and in an embodiment in which a reactive group for curing treatment or a functional group that becomes a crosslinking point is introduced into the polymer, it is preferably about 95% by weight or less, more preferably about 90% by weight or less, and even more preferably about 85% by weight or less (e.g., about 75% by weight or less).
[0053] The secondary monomer having copolymerizability with the main monomer alkyl (meth)acrylate can be useful for introducing crosslinking points into the acrylic polymer or for increasing the cohesive strength of the acrylic polymer. In the technology disclosed herein, it is preferable to adopt as the secondary monomer a monomer having a functional group (functional group A) capable of reacting with the functional group (functional group B) of the carbon-carbon double bond-containing monomer described below. As the secondary monomer, for example, the following functional group-containing monomer components can be used alone or in combination of two or more. Carboxy group-containing monomers: for example, ethylenically unsaturated monocarboxylic acids such as acrylic acid (AA), methacrylic acid (MAA), crotonic acid, etc.; ethylenically unsaturated dicarboxylic acids such as maleic acid, itaconic acid, citraconic acid, etc., and their anhydrides (maleic anhydride, itaconic anhydride, etc.). Hydroxyl group-containing monomers: for example, hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, etc.; unsaturated alcohols such as vinyl alcohol, allyl alcohol, etc.; ether compounds such as 2-hydroxyethyl vinyl ether, 4-hydroxybutyl vinyl ether, diethylene glycol monovinyl ether, etc. Amide group-containing monomers: for example, (meth)acrylamide, N,N-dimethyl(meth)acrylamide, N-butyl(meth)acrylamide, N-methylol(meth)acrylamide, N-methylolpropane(meth)acrylamide, N-methoxymethyl(meth)acrylamide, N-butoxymethyl(meth)acrylamide. Amino group-containing monomers: for example, aminoethyl (meth)acrylate, N,N-dimethylaminoethyl (meth)acrylate, t-butylaminoethyl (meth)acrylate. Epoxy group-containing monomers: for example, glycidyl (meth)acrylate, methyl glycidyl (meth)acrylate, allyl glycidyl ether. Cyano group-containing monomers: for example acrylonitrile, methacrylonitrile. Keto group-containing monomers: for example, diacetone (meth)acrylamide, diacetone (meth)acrylate, vinyl methyl ketone, vinyl ethyl ketone, allyl acetoacetate, vinyl acetoacetate. Monomers having a nitrogen atom-containing ring: for example, N-vinyl-2-pyrrolidone, N-methylvinylpyrrolidone, N-vinylpyridine, N-vinylpiperidone, N-vinylpyrimidine, N-vinylpiperazine, N-vinylpyrazine, N-vinylpyrrole, N-vinylimidazole, N-vinyloxazole, N-vinylmorpholine, N-vinylcaprolactam, N-(meth)acryloylmorpholine. Alkoxysilyl group-containing monomers: for example, 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropyltriethoxysilane, 3-(meth)acryloxypropylmethyldimethoxysilane, 3-(meth)acryloxypropylmethyldiethoxysilane. Isocyanate group-containing monomers: (meth)acryloyl isocyanate, 2-(meth)acryloyloxyethyl isocyanate, m-isopropenyl-α,α-dimethylbenzyl isocyanate.
[0054] From the viewpoint of improving cohesion, it is preferable to use a hydroxyl group-containing monomer as the secondary monomer, and it is more preferable that the hydroxyl group-containing monomer is a hydroxyalkyl (meth)acrylate such as 2-hydroxyethyl acrylate (HEA) or 4-hydroxybutyl acrylate (4HBA).
[0055] In addition, in the technology disclosed herein, it is desirable to limit the amount of carboxyl group-containing monomers (e.g., AA and MAA) or monomers having a nitrogen atom-containing ring (e.g., N-acryloylmorpholine) used as secondary monomers from the viewpoint of reducing adhesion after curing treatment. In some embodiments, the ratio of the carboxyl group-containing monomer in the total monomer components for preparing the acrylic polymer is less than 10% by weight, preferably less than 5% by weight, more preferably less than 1% by weight, and even more preferably less than 0.1% by weight. The technology disclosed herein can be preferably implemented in an embodiment in which the secondary monomers used in preparing the acrylic polymer do not substantially contain a carboxyl group-containing monomer. In some embodiments, the ratio of the monomer having a nitrogen atom-containing ring in the total monomer components for preparing the acrylic polymer is less than 25% by weight, appropriately less than 10% by weight, preferably less than 5% by weight, more preferably less than 1% by weight, and even more preferably less than 0.1% by weight. The technology disclosed herein can be preferably implemented in an embodiment in which the secondary monomers used in preparing the acrylic polymer do not substantially contain a monomer having a nitrogen atom-containing ring.
[0056] The amount of the sub-monomer is not particularly limited and may be appropriately selected so as to realize the desired cohesive strength. Usually, from the viewpoint of achieving a good balance between cohesive strength and other properties (e.g., adhesiveness), the amount of the sub-monomer (preferably a hydroxyl group-containing monomer) is suitably 0.1% by weight or more of the total monomer components of the acrylic polymer, and preferably 0.3% by weight or more (e.g., 1% by weight or more). In addition, the amount of the sub-monomer (preferably a hydroxyl group-containing monomer) is suitably 30% by weight or less of the total monomer components, and preferably 10% by weight or less (e.g., 5% by weight or less).
[0057] In addition, when an acrylic polymer having a carbon-carbon double bond is used as the polymer, it is preferable to use, as the secondary monomer, a secondary monomer having a functional group (functional group A) capable of reacting with a functional group (functional group B) of a compound having a carbon-carbon double bond, which will be described later. In such a case, the type of secondary monomer is determined by the type of the compound. As the secondary monomer having functional group A, for example, a carboxyl group-containing monomer, an epoxy group-containing monomer, a hydroxyl group-containing monomer, or an isocyanate group-containing monomer is preferable, and a hydroxyl group-containing monomer is particularly preferable. By using a hydroxyl group-containing monomer as the secondary monomer, the acrylic polymer has a hydroxyl group. On the other hand, by using an isocyanate group-containing monomer as the compound having a carbon-carbon double bond, the hydroxyl group of the acrylic polymer reacts with the isocyanate group of the compound, and a carbon-carbon double bond derived from the compound is introduced into the acrylic polymer.
[0058] In addition, when a secondary monomer is used for the purpose of reacting with a compound having a carbon-carbon double bond, the amount of the secondary monomer (preferably a hydroxyl group-containing monomer) is suitably about 1% by weight or more of the total monomer components from the viewpoint of reducing the adhesive strength after curing treatment and increasing the elastic modulus of the adhesive layer, preferably about 5% by weight or more, more preferably about 10% by weight or more, and even more preferably about 12% by weight or more (e.g., about 14% by weight or more). In addition, from the viewpoint of maintaining good adhesive properties such as adhesion, the amount of the secondary monomer is suitably about 40% by weight or less of the total monomer components, preferably about 30% by weight or less, more preferably about 20% by weight or less, and may be, for example, about 15% by weight or less.
[0059] For the purpose of increasing the cohesive strength of the acrylic polymer, copolymerization components other than the above-mentioned secondary monomers may be used. Examples of such copolymerization components include vinyl ester monomers such as vinyl acetate and vinyl propionate; aromatic vinyl compounds such as styrene, substituted styrenes (α-methylstyrene, etc.), and vinyl toluene; cycloalkyl (meth)acrylates such as cyclohexyl (meth)acrylate, cyclopentyl di(meth)acrylate, and isobornyl (meth)acrylate; aromatic ring-containing (meth)acrylates such as aryl (meth)acrylates (e.g., phenyl (meth)acrylate), aryloxyalkyl (meth)acrylates (e.g., phenoxyethyl (meth)acrylate), and arylalkyl (meth)acrylates (e.g., benzyl (meth)acrylate); olefin monomers such as ethylene, propylene, isoprene, butadiene, and isobutylene; chlorine-containing monomers such as vinyl chloride and vinylidene chloride; alkoxy group-containing monomers such as methoxyethyl (meth)acrylate and ethoxyethyl (meth)acrylate; vinyl ether monomers such as methyl vinyl ether and ethyl vinyl ether; and the like. The copolymerization components other than these sub-monomers can be used alone or in combination of two or more. The amount of such other copolymerization components is not particularly limited and may be appropriately selected depending on the purpose and application, but is preferably 20% by weight or less (e.g., 2 to 20% by weight, typically 3 to 10% by weight) of the total monomer components of the acrylic polymer.
[0060] Furthermore, for the purpose of crosslinking the acrylic polymer, a polyfunctional monomer can be used as a copolymerizable component. As the polyfunctional monomer, one or more of hexanediol di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, epoxy acrylate, polyester acrylate, urethane acrylate, etc. can be used. The amount of the polyfunctional monomer may be appropriately selected according to the purpose and application, and is not particularly limited, but is preferably about 30% by weight or less (for example, 20% by weight or less, typically 10% by weight or less) of the total monomer components of the acrylic polymer.
[0061] The method for obtaining an acrylic polymer having the above monomer composition is not particularly limited, and various polymerization methods known as synthesis methods for acrylic polymers, such as solution polymerization, emulsion polymerization, bulk polymerization, and suspension polymerization, can be appropriately adopted. For example, a solution polymerization method can be preferably adopted. As a monomer supply method when performing solution polymerization, a lump-sum charging method in which all monomer raw materials are supplied at once, a continuous supply (dropping) method, a divided supply (dropping) method, and the like can be appropriately adopted. The solvent used in solution polymerization can be appropriately selected from known or commonly used organic solvents such as toluene and ethyl acetate. The polymerization temperature can be appropriately selected depending on the type of monomer and solvent used, the type of polymerization initiator, and the like, and can be, for example, about 20°C to 120°C (typically 40°C to 80°C).
[0062] The initiator used in the polymerization can be appropriately selected from known or conventional polymerization initiators depending on the type of polymerization method. Examples of peroxide initiators include organic peroxides such as diacyl peroxides, peroxy esters, peroxy dicarbonates, monoperoxy carbonates, peroxy ketals, dialkyl peroxides, hydroperoxides, and ketone peroxides, and hydrogen peroxide. In addition, polymerization initiators such as azo initiators such as 2,2'-azobisisobutyronitrile (AIBN), persulfates such as potassium persulfate and ammonium persulfate, substituted ethane compounds such as phenyl-substituted ethane, aromatic carbonyl compounds, and redox compounds (redox initiators) formed by combining peroxides and reducing agents can also be used. Examples of redox initiators include a combination of peroxide and ascorbic acid (such as a combination of hydrogen peroxide and ascorbic acid), a combination of peroxide and iron (II) salt (such as a combination of hydrogen peroxide and iron (II) salt), a combination of persulfate and sodium hydrogen sulfite, etc. Also, the polymerization initiators exemplified as radical generators may be used. The polymerization initiators may be used alone or in combination of two or more. Among them, peroxide initiators are preferred, diacyl peroxides and peroxy esters are more preferred, and dibenzoyl peroxide (BPO), 1,1,3,3-tetramethylbutylperoxy-2-ethylhexanoate, and t-hexylperoxy-2-ethylhexanoate are even more preferred.
[0063] The amount of the polymerization initiator used may be a normal amount, and may be selected, for example, from the range of about 0.005 to 1 part by weight (typically 0.01 to 1 part by weight) relative to 100 parts by weight of the total monomer components. When the polymerization initiator is also used as a radical generator, the amount of the polymerization initiator used may be set taking this into consideration.
[0064] (Acrylic polymer with carbon-carbon double bonds) In addition, the acrylic polymer disclosed herein is preferably an acrylic polymer having a carbon-carbon double bond from the viewpoint of the decrease in adhesive strength after heat-curing treatment and the increase in the elastic modulus of the adhesive layer. Acrylic polymers are also advantageous in that the monomer raw material can be selected with a high degree of freedom and the physical properties can be easily controlled. The method of using the acrylic polymer having the carbon-carbon double bond corresponds to the method (1) of having a carbon-carbon double bond present in the adhesive layer described below.
[0065] The method of introducing a carbon-carbon double bond into an acrylic polymer is not particularly limited. For example, a method of reacting (typically condensation, addition reaction) a compound having a functional group (functional group B) and a carbon-carbon double bond that can react with a functional group (functional group A) introduced into an acrylic polymer by copolymerization so that the carbon-carbon double bond does not disappear can be preferably adopted. Examples of combinations of functional group A and functional group B include a combination of a carboxy group and an epoxy group, a combination of a carboxy group and an aziridyl group, and a combination of a hydroxyl group and an isocyanate group. Among them, from the viewpoint of reaction tracing, a combination of a hydroxyl group and an isocyanate group is preferred. From the viewpoint of polymer design, etc., a combination in which the acrylic polymer has a hydroxyl group and the above compound has an isocyanate group is particularly preferred.
[0066] The compound having a carbon-carbon double bond may have a functional group B capable of reacting with the functional group A, as described above. Suitable examples of such compounds include the isocyanate group-containing monomers (isocyanate group-containing compounds) exemplified as the secondary monomers that can be used in the polymerization of acrylic polymers. Among these, 2-(meth)acryloyloxyethyl isocyanate is more preferred. The isocyanate group of the isocyanate group-containing compound having a carbon-carbon double bond reacts with the hydroxyl group of the acrylic polymer to form a bond (typically a urethane bond), thereby suitably realizing an acrylic polymer having a carbon-carbon double bond.
[0067] The amount of the isocyanate group-containing monomer to be blended is determined based on the above-mentioned molar ratio (MA / M B ) can be appropriately set within a range that satisfies the above. For example, it is appropriate that the amount of the isocyanate group-containing monomer is about 1 part by weight or more (for example, 5 parts by weight or more, typically 10 parts by weight or more) relative to 100 parts by weight of an acrylic polymer having a hydroxyl group (typically an acrylic polymer before the introduction of a carbon-carbon double bond), and from the viewpoint of the decrease in adhesive strength after the heat-curing treatment and the increase in the elastic modulus of the adhesive layer, it is preferably about 15 parts by weight or more, more preferably about 18 parts by weight or more, and even more preferably about 21 parts by weight or more. In addition, the upper limit of the amount of the isocyanate group-containing monomer is not particularly limited, and it is appropriate that the amount is about 40 parts by weight or less relative to 100 parts by weight of the acrylic polymer having a hydroxyl group, preferably about 35 parts by weight or less, more preferably about 30 parts by weight or less, and may be, for example, about 25 parts by weight or less.
[0068] The amount of the isocyanate group-containing monomer is preferably about 1% by weight or more (about 3% by weight or more) of the total monomer components constituting the polymer (typically an acrylic polymer incorporating an isocyanate group-containing monomer) contained in the adhesive layer, and from the viewpoint of the decrease in adhesive strength after heat-curing treatment and the increase in the elastic modulus of the adhesive layer, it is preferably about 5% by weight or more, more preferably about 10% by weight or more, even more preferably about 15% by weight or more, and may be, for example, about 18% by weight or more. The upper limit of the amount of the isocyanate group-containing monomer is not particularly limited, and from the viewpoint of adhesive properties such as adhesive strength, it is preferably about 40% by weight or less, preferably about 35% by weight or less, more preferably about 30% by weight or less, even more preferably about 25% by weight or less, and may be, for example, about 20% by weight or less.
[0069] The weight average molecular weight (Mw) of the polymer (preferably an acrylic polymer) in the technology disclosed herein is not particularly limited. From the viewpoint of preventing adhesive residue on the adherend surface upon peeling, the Mw is about 10×10 4 It is appropriate that the number of pixels is equal to or larger than 20×10. 4 More preferably, about 30×104 On the other hand, from the viewpoint of improving the adhesion to the adherend, the above Mw is set to about 500×10 4 It is appropriate to set the value to less than 100×10 4 Less than or equal to 70×10 4 In this specification, Mw refers to a value calculated in terms of standard polystyrene obtained by gel permeation chromatography (GPC).
[0070] (Monomers / oligomers with carbon-carbon double bonds) The technology disclosed herein may also be preferably implemented in an embodiment having a pressure-sensitive adhesive layer containing a monomer / oligomer having a carbon-carbon double bond. As the above-mentioned monomer / oligomer, those mentioned above can be preferably used. In an embodiment using an acrylic polymer as the polymer, it is preferable to use one or more of the above-mentioned (meth)acryloyl group-containing compounds or multimers (e.g., dimer to pentamer) of the (meth)acryloyl group-containing compounds. The multimer may be, for example, a polyfunctional (typically difunctional to pentafunctional) compound. The method using the above-mentioned monomer / oligomer having a carbon-carbon double bond corresponds to the method (2) of having a carbon-carbon double bond present in the pressure-sensitive adhesive layer described later.
[0071] (Other polymers) When the adhesive layer disclosed herein contains an acrylic polymer, it may contain a polymer other than the acrylic polymer in addition to the acrylic polymer. As the polymer other than the acrylic polymer, a polymer other than the acrylic polymer among the various polymers exemplified as the polymer that can be contained in the adhesive layer is preferably a polymer having a carbon-carbon double bond. When the adhesive layer disclosed herein contains a polymer other than the acrylic polymer in addition to the acrylic polymer, the content of the polymer other than the acrylic polymer is suitably 100 parts by weight or less relative to 100 parts by weight of the acrylic polymer, preferably 50 parts by weight or less, more preferably 30 parts by weight or less, and even more preferably 10 parts by weight or less. The content of the polymer other than the acrylic polymer may be 5 parts by weight or less, or may be 1 part by weight or less relative to 100 parts by weight of the acrylic polymer. The technology disclosed herein may be preferably implemented, for example, in an embodiment in which 99.5 to 100% by weight of the polymer contained in the adhesive layer is an acrylic polymer.
[0072] (carbon-carbon double bond) In some preferred embodiments, the adhesive layer contains a carbon-carbon double bond. In this embodiment, the adhesive layer is subjected to a curing treatment, whereby the carbon-carbon double bonds present in the adhesive layer react to reduce the adhesive strength and improve the elastic modulus. The carbon-carbon double bond is chemically stable and does not react with moisture or acidity in the air in a normal storage environment that can be applied industrially. On the other hand, for example, when a photopolymerization initiator is contained in the adhesive layer and the adhesive layer is irradiated with active energy rays, or when a thermal polymerization initiator is contained in the adhesive layer and the adhesive layer is heated to generate radicals, the adhesive layer reacts (for example, a polymerization reaction or a crosslinking reaction). By employing an adhesive layer containing a carbon-carbon double bond, the adhesive strength can be rapidly reduced under a specified curing treatment condition.
[0073] In the embodiment in which the adhesive layer contains a carbon-carbon double bond, the form of the carbon-carbon double bond in the adhesive layer is not particularly limited. The carbon-carbon double bond may be present, for example, in a polymer (typically the above-mentioned base polymer), an oligomer, or a monomer. Among them, a polymer with relatively low mobility in the adhesive layer is preferable. The polymer may be a polymer having a carbon-carbon double bond in a side chain or a main chain. Here, having a carbon-carbon double bond in the main chain includes the presence of a carbon-carbon double bond in the main chain skeleton of the polymer and the presence of a carbon-carbon double bond at the main chain end. As with the polymer, the oligomer may be exemplified by an oligomer having a carbon-carbon double bond in a side chain or a main chain (in the main chain skeleton, at the main chain end).
[0074] The form of the carbon-carbon double bond that may be present in the side chain of the polymer or oligomer, or the form of the carbon-carbon double bond that may be present in the monomer is not particularly limited, and for example, the carbon-carbon double bond may be present in the form of a group (typically an organic group) containing a vinyl group. The vinyl group-containing group may be a vinyl group, an allyl group, or a (meth)acryloyl group. The method of introducing the carbon-carbon double bond into the polymer or oligomer is not particularly limited, and an appropriate method may be selected from among methods known to those skilled in the art. From the viewpoint of molecular design, etc., a method of introducing a carbon-carbon double bond into the side chain of the polymer or oligomer is preferred. In this specification, the main chain of a polymer or oligomer refers to the chain structure that forms the skeleton of the polymer or oligomer, and the side chain of a polymer or oligomer refers to a group (pendant, side group) that bonds to the main chain or a molecular chain that can be considered as a pendant.
[0075] In the technology disclosed herein, typical methods for causing carbon-carbon double bonds to exist in the pressure-sensitive adhesive layer include the following methods. (1) A method of using a polymer having a carbon-carbon double bond as a polymer for forming a pressure-sensitive adhesive layer. Specifically, this method comprises adding a polymer having a carbon-carbon double bond to a pressure-sensitive adhesive composition, and forming a pressure-sensitive adhesive layer using the pressure-sensitive adhesive composition. (2) A method of incorporating a polymer, oligomer and / or monomer having a carbon-carbon double bond in the adhesive layer in addition to the polymer forming the adhesive layer. Specifically, this method involves adding an appropriate amount of the polymer, oligomer and / or monomer to an adhesive composition, and forming an adhesive layer using the adhesive composition. The above (1) and (2) may be used in combination.
[0076] An example of an adhesive layer having a carbon-carbon double bond is an adhesive layer having a structure in which a group having a carbon-carbon double bond (reactive group, specifically, a radical reactive group) is present. By allowing the reactive group to exist in the adhesive layer, the reactive group reacts under curing treatment conditions to reduce the adhesive strength and increase the elasticity of the adhesive layer. It is preferable that the reactive group is substantially inactive (non-reactive) in a state before curing treatment (for example, at 40°C or less at atmospheric pressure, typically at room temperature (for example, 25°C)).
[0077] A suitable example of a pressure-sensitive adhesive layer having a carbon-carbon double bond is a pressure-sensitive adhesive layer having the general formula (1): [ka] (wherein R is hydrogen or a methyl group); the compound includes a polymer (typically a base polymer), an oligomer, and a monomer. The adhesive layer containing the compound may reduce the adhesive strength by reacting the carbon-carbon double bond in the reactive group in the compound under curing treatment conditions. The elastic modulus of the adhesive layer is also increased. The compound is preferably a polymer.
[0078] When the compound is a polymer (typically a base polymer), that is, when the polymer (typically a base polymer) has a reactive group represented by the general formula (1), the method of introducing the reactive group into the polymer (typically a base polymer) is not particularly limited, and an appropriate method can be selected from methods known to those skilled in the art. For example, the same method as the above-mentioned method of introducing a reactive group into an acrylic polymer can be preferably adopted. When the compound is an oligomer, the reactive group can be introduced into the oligomer by adopting the same method as the case of the polymer. When the compound is a monomer, a monomer having the reactive group can be obtained or synthesized and incorporated into the adhesive layer.
[0079] The polymer having a carbon-carbon double bond is not particularly limited, and an appropriate polymer can be selected from the above-mentioned polymers in consideration of the properties of the adhesive layer, etc. When the above-mentioned polymer is a polymer not containing a carbon-carbon double bond, a polymer not containing a carbon-carbon double bond in which a carbon-carbon double bond has been introduced by a method such as chemical modification can be preferably used.
[0080] A specific example of the method for introducing the carbon-carbon double bond into the polymer is a method in which a monomer having a functional group (hereinafter also referred to as "functional group A") is copolymerized in the polymer, and then a compound having a functional group (hereinafter also referred to as "functional group B") that can react with the functional group A and a carbon-carbon double bond is reacted (typically by condensation or addition reaction) so that the carbon-carbon double bond does not disappear. Examples of combinations of the functional group A and the functional group B include a combination of a carboxy group and an epoxy group, a combination of a carboxy group and an aziridyl group, and a combination of a hydroxyl group and an isocyanate group. Among these, from the viewpoint of reaction tracing, a combination of a hydroxyl group and an isocyanate group is preferable. In addition, as for the combination of the functional groups A and B, one of the functional groups in the combination may be the functional group A and the other may be the functional group B, or one of the functional groups may be the functional group B and the other may be the functional group A, as long as the combination is a combination that can obtain a polymer having a carbon-carbon double bond. For example, in the case of a combination of a hydroxyl group and an isocyanate group, the functional group A may be a hydroxyl group (in which case the functional group B is an isocyanate group) or an isocyanate group (in which case the functional group B is a hydroxyl group). Among these, a combination in which the polymer has a hydroxyl group and the compound has an isocyanate group is preferred. This combination is particularly preferred when the polymer is an acrylic polymer.
[0081] In addition, when the polymer is a vinyl alcohol-based polymer (typically polyvinyl alcohol), a suitable example is a method in which a vinyl alcohol-based polymer (typically a vinyl alcohol-based polymer not containing a carbon-carbon double bond) is reacted with a vinyl halide such as vinyl bromide or an allyl halide such as allyl bromide. In this method, the reaction is carried out under suitable basic conditions, and a vinyl alcohol-based polymer containing a vinyl group in the side chain is obtained by the reaction. In addition, a method of preparing a polymer having a carbon-carbon double bond using a microorganism that produces a polymer as disclosed in Japanese Patent No. 4502363 may be adopted. The various conditions in this method, such as the microorganism species and the microorganism culture conditions, may be set by adopting the conditions described in the above patent publication, or by appropriately modifying them within the scope of the technical common sense of a person skilled in the art.
[0082] The moles of the functional group A (M A ) and moles of functional group B (M B ) molar ratio (M A / M B Since the molar ratio (M) is set depending on the reactivity of the two, it is not limited to a specific range, and is usually set to 0.2 or more, preferably 0.5 or more (e.g., 0.7 or more, typically 1.0 or more), and is usually set to 10 or less, preferably 5.0 or less (e.g., 3.0 or less, typically 2.5 or less). In some embodiments, the molar ratio (M A / M B ) may be 2.0 or less, 1.5 or less, or 1.3 or less (for example, 1.1 or less). In order to increase the contact opportunity between the functional group A and the functional group B, a larger amount of the functional group B-containing compound having a carbon-carbon double bond may be blended. In this case, the molar ratio (M A / M B It is preferable that the molar ratio (M A / M B ) is greater than 1, i.e., the molar ratio (M A / M B The amount of the compound having the functional group B is preferably in the above-mentioned molar ratio (M A / M B), it is appropriate to use about 1 part by weight or more, for example about 5 parts by weight or more (typically about 10 parts by weight or more), preferably about 12 parts by weight or more, more preferably about 15 parts by weight or more, even more preferably about 18 parts by weight or more, and may be about 21 parts by weight or more (for example, 23 parts by weight or more), relative to 100 parts by weight of the polymer having the functional group A (typically, the polymer before the carbon-carbon double bond is introduced), within the range satisfying the above-mentioned molar ratio (M A / M B ) or a compound containing a functional group B having a carbon-carbon double bond can be preferably used.
[0083] The polymer having a carbon-carbon double bond may be, for example, a diene-based polymer (typically a conjugated diene-based polymer). A diene-based polymer (typically a conjugated diene-based polymer) is typically a polymer obtained by polymerizing or copolymerizing a diene (typically a conjugated diene). Examples of the diene-based polymer (typically a conjugated diene-based polymer) include butadiene-based polymers such as polybutadiene and styrene-butadiene copolymer; isoprene-based polymers such as polyisoprene and styrene-isoprene copolymer; and chloroprene-based polymers such as polychloroprene.
[0084] In addition, from the viewpoint of easy reactivity, an external double bond is more preferable than an internal double bond. Here, the internal double bond refers to a double bond that exists in a state that it is incorporated inside the main chain of a polymer or oligomer. In this carbon-carbon double bond, both carbon atoms constitute the main chain. In addition, the external double bond refers to a double bond that exists outside the molecular chain (e.g., the main chain) of a polymer or oligomer. Note that, when a carbon-carbon double bond exists at the end of the main chain of a polymer or oligomer, the double bond is an external double bond.
[0085] When the technology disclosed herein is implemented in an embodiment with a pressure-sensitive adhesive layer containing a polymer (typically a base polymer) having a carbon-carbon double bond, the content of the polymer (typically a base polymer) having a carbon-carbon double bond in the pressure-sensitive adhesive layer may be set to achieve a target decrease in adhesive strength after heat-curing treatment, and is not limited to a specific range. In some embodiments, the content of the polymer having a carbon-carbon double bond in the pressure-sensitive adhesive layer is about 10% by weight or more, and is preferably about 50% by weight or more (for example, about 70% by weight or more), and from the viewpoint of the decrease in adhesive strength after heat-curing treatment, it is preferably about 90% by weight or more, more preferably about 95% by weight or more, even more preferably about 97% by weight or more, and may be about 99% by weight or more (for example, 99 to 100% by weight).
[0086] In addition, examples of the monomers and oligomers having a carbon-carbon double bond disclosed herein (hereinafter, simply referred to as monomers / oligomers) include (meth)acryloyl group-containing compounds such as urethane oligomers, urethane (meth)acrylates, trimethylolpropane tri(meth)acrylates, tetramethylolmethane tetra(meth)acrylates, pentaerythritol tri(meth)acrylates, pentaerythritol tetra(meth)acrylates, dipentaerythritol monohydroxypenta(meth)acrylates, dipentaerythritol hexa(meth)acrylates, 1,4-butanediol di(meth)acrylates, 1,6-butanediol di(meth)acrylates, and polyethylene glycol di(meth)acrylates; dimers to pentamers of the (meth)acryloyl group-containing compounds; and the like. These can be used alone or in combination of two or more. The oligomer having a carbon-carbon double bond may also be one or more of oligomers such as urethane-based oligomers, polyether-based oligomers, polyester-based oligomers, polycarbonate-based oligomers, and polybutadiene-based oligomers.
[0087] In this specification, oligomer means a polymer having a molecular weight of 3.0×10 4 The molecular weight of the oligomer is preferably 100 or more, and is preferably 1.0×10 4 As the molecular weight of the oligomer, a weight average molecular weight (Mw) calculated in terms of standard polystyrene determined by GPC, or a molecular weight calculated from a chemical formula is used.
[0088] When the technology disclosed herein is implemented in an embodiment having an adhesive layer containing a monomer / oligomer having a carbon-carbon double bond, the content of the monomer / oligomer having a carbon-carbon double bond in the adhesive layer is set so as to achieve the targeted reduction in adhesive strength after heat-curing treatment, and is not limited to a specific range.
[0089] (Radical generator) In addition, the adhesive layer disclosed herein preferably contains a radical generator. It is known that, regardless of the presence or absence of carbon-carbon double bonds, radicals are generated by the cleavage of molecular bonds of polymers and the like or by oxidation with oxygen in the air when heated ("Measures to Prevent Polymer Deterioration and Decomposition <by Resin> and the Latest Modification and Stabilization Technology" Polymer Properties Research Society, published in 1981). Therefore, depending on the curing conditions, it can be considered that the radical generator is not an essential component. However, from the viewpoint of quickly and reliably reducing the adhesive strength by the curing process, it is preferable to actively include a radical generator in the adhesive layer. By including a radical generator in the adhesive layer, radicals are generated from the radical generator during the curing process, which react with the carbon-carbon double bonds present in the adhesive layer, and the curing of the adhesive layer proceeds quickly.
[0090] In this specification, the term "radical generator" refers to an agent that generates radicals by, for example, decomposing itself under curing treatment conditions. A suitable example is a photopolymerization initiator used in radical polymerization. Hereinafter, an agent that generates radicals by, for example, decomposing itself upon irradiation with active energy rays such as UV rays may be referred to as an active energy ray irradiation radical generator (typically a photoradical generator). The radical generators may be used alone or in combination of two or more.
[0091] In some preferred embodiments, a photopolymerization initiator is used as the radical generator. In this embodiment, the pressure-sensitive adhesive layer attached to the adherend is irradiated with active energy rays (e.g., UV), whereby the pressure-sensitive adhesive layer cures and shrinks, and a high level of prevention of adhesive residue can be preferably achieved. As the photopolymerization initiator, for example, one or more of ketal-based photopolymerization initiators, acetophenone-based photopolymerization initiators, benzoin ether-based photopolymerization initiators, acylphosphine oxide-based photopolymerization initiators, α-ketol-based photopolymerization initiators, aromatic sulfonyl chloride-based photopolymerization initiators, oxime ester-based photopolymerization initiators, benzoin-based photopolymerization initiators, benzyl-based photopolymerization initiators, benzophenone-based photopolymerization initiators, alkylphenone-based photopolymerization initiators, and thioxanthone-based photopolymerization initiators can be used.
[0092] The photopolymerization initiator preferably has a hydroxyl group in the molecule. As such a hydroxyl group-containing photopolymerization initiator, a photopolymerization initiator having a hydroxyl group among the above-mentioned photopolymerization initiators can be preferably used. For example, benzophenone derivatives, alkylphenone derivatives, and acetophenone derivatives can be mentioned as suitable examples. Benzophenone derivatives include, for example, o-acryloxybenzophenone, p-acryloxybenzophenone, o-methacryloxybenzophenone, p-methacryloxybenzophenone, and p-(meth)acryloxyethoxybenzophenone. Benzophenone-4-carboxylate esters of acrylates such as 1,4-butanediol mono(meth)acrylate, 1,2-ethanediol mono(meth)acrylate, and 1,8-octanediol mono(meth)acrylate can also be used. Alkylphenone derivatives include, for example, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one, and 2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)-benzyl]phenyl}-2-methyl-propan-1-one. Acetophenone derivatives include, for example, 1-hydroxycyclohexyl-phenyl-ketone. The photopolymerization initiators can be used alone or in combination of two or more. Among them, 1-hydroxycyclohexyl-phenyl-ketone and 2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)-benzyl]phenyl}-2-methyl-propan-1-one are preferred because of their excellent curing speed and thick-film curing properties.
[0093] Suitable examples of alkylphenone-based photopolymerization initiators include benzyl ketal-based photopolymerization initiators, hydroxyalkylphenone-based photopolymerization initiators (typically α-hydroxyalkylphenone), hydroxyacetophenone-based photopolymerization initiators (typically α-hydroxyacetophenone), and aminoalkylphenone-based photopolymerization initiators (typically α-aminoalkylphenone). These can be used alone or in combination of two or more. Among them, hydroxyalkylphenone-based photopolymerization initiators and aminoalkylphenone-based photopolymerization initiators are preferred. A specific example of a hydroxyalkylphenone-based photopolymerization initiator is the above-mentioned 2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)-benzyl]phenyl}-2-methyl-propan-1-one, and a specific example of an aminoalkylphenone-based photopolymerization initiator is 2-benzyl-2-(dimethylamino)-1-(4-morpholinophenyl)-1-butanone. Other preferred examples include acylphosphine oxide photopolymerization initiators such as bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-2,4-di-n-butoxyphenylphosphine oxide, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, and bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide. In addition, oxime ester photopolymerization initiators such as 1,2-octanedione, 1-[4-(phenylthio)phenyl]-2-(o-benzoyloxime), ethanone, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]-1-(o-acetyloxime) and the like can also be preferably used.
[0094] In some embodiments, a photopolymerization initiator that is difficult to decompose by heating or difficult to generate radicals by heating is used as the active energy ray irradiation radical generator. For example, a heat-resistant photopolymerization initiator having a 10% weight reduction temperature of 200°C or higher is used as the photopolymerization initiator. By using such a heat-resistant photopolymerization initiator, even if it is exposed to high temperatures before the curing treatment, the adhesive force can be effectively reduced by the curing treatment with active energy rays. The 10% weight reduction temperature means the environmental temperature at which the weight of the photopolymerization initiator is reduced by 10% by weight compared to the weight before the temperature increase (i.e., the weight of the photopolymerization initiator is 90% by weight compared to the weight before the temperature increase) when the photopolymerization initiator is placed under a nitrogen atmosphere and the environmental temperature is increased from 23°C to 300°C at a heating rate of 2°C / min. The 10% weight reduction temperature of the photopolymerization initiator is more preferably 210°C or higher, and even more preferably 220°C or higher. Examples of photopolymerization initiators having a 10% weight loss temperature in this range include those manufactured by BASF under the trade names "Irgacure 369," "Irgacure 379ex," "Irgacure 819," "Irgacure OXE2," and "Irgacure 127"; those manufactured by Lamberti under the trade names "Esacure one" and "Esacure 1001m"; and those manufactured by Asahi Denka Kogyo Co., Ltd. under the trade names "ADEKA OPTOMER N-1414," "ADEKA OPTOMER N-1606," and "ADEKA OPTOMER N-1717."
[0095] When the adhesive layer disclosed herein contains a radical generator, the method of addition is not particularly limited. For example, it is preferable to add and mix the radical generator into the adhesive composition, typically into a liquid containing a polymer (polymer in which polymerization has been completed). In this method, the radical generator (preferably an active energy ray irradiation radical generator) can be added to the composition together with other added components (e.g., a crosslinking agent, etc.). Alternatively, a method of adding a polymerization initiator that can also be a radical generator during polymer polymerization can be mentioned. In this method, the polymerization initiator is added so that a predetermined amount remains after polymerization. The remaining amount of the polymerization initiator (amount of the radical generator present) can be adjusted not only by the amount of the polymerization initiator added, but also by the polymer polymerization conditions, drying and curing conditions during the formation of the adhesive layer, etc.
[0096] When the adhesive layer disclosed herein contains a radical generator, the content (addition amount) of the radical generator may be appropriately determined according to the curing treatment conditions, etc., and is not particularly limited. The content of the radical generator in the adhesive layer is preferably about 0.01% by weight or more (for example, about 0.1% by weight or more, typically about 0.5% by weight or more) from the viewpoint of accurately progressing the curing reaction, and is preferably about 1% by weight or more, more preferably about 1.5% by weight or more, and even more preferably about 2% by weight or more. The upper limit of the content of the radical generator is not particularly limited, and is preferably about 10% by weight or less (for example, about 8% by weight or less, typically about 5% by weight or less).
[0097] (Crosslinking agent) The adhesive composition used to form the adhesive layer preferably contains a crosslinking agent in addition to the above polymer, from the viewpoint of improving the cohesiveness of the adhesive layer. The type of crosslinking agent is not particularly limited, and examples thereof include isocyanate-based crosslinking agents, epoxy-based crosslinking agents, oxazoline-based crosslinking agents, aziridine-based crosslinking agents, melamine-based crosslinking agents, peroxide-based crosslinking agents, urea-based crosslinking agents, metal alkoxide-based crosslinking agents, metal chelate-based crosslinking agents, metal salt-based crosslinking agents, carbodiimide-based crosslinking agents, and amine-based crosslinking agents. These crosslinking agents can be used alone or in combination of two or more. Among them, isocyanate-based crosslinking agents and metal chelate-based crosslinking agents are preferred.
[0098] Examples of isocyanate crosslinking agents include polyfunctional isocyanate compounds having two or more functionalities. For example, aromatic isocyanates such as tolylene diisocyanate, xylene diisocyanate, polymethylene polyphenyl diisocyanate, tris(p-isocyanatophenyl)thiophosphate, diphenylmethane diisocyanate, etc.; alicyclic isocyanates such as isophorone diisocyanate, etc.; aliphatic isocyanates such as hexamethylene diisocyanate, etc. Examples of commercially available products include isocyanate adducts such as trimethylolpropane / tolylene diisocyanate trimer adduct (manufactured by Tosoh Corporation, product name "Coronate L"), trimethylolpropane / hexamethylene diisocyanate trimer adduct (manufactured by Tosoh Corporation, product name "Coronate HL"), and isocyanurate of hexamethylene diisocyanate (manufactured by Tosoh Corporation, product name "Coronate HX"), etc.
[0099] The metal chelate crosslinking agent may typically have a structure in which a polyvalent metal is covalently or coordinately bonded to an organic compound. Examples of the polyvalent metal atom include Al, Zr, Co, Cu, Fe, Ni, V, Zn, In, Ca, Mg, Mn, Y, Ce, Ba, Mo, La, Sn, and Ti. Among these, Al, Zr, and Ti are preferred. Examples of the organic compound include alkyl esters, alcohol compounds, carboxylic acid compounds, ether compounds, and ketone compounds. The metal chelate crosslinking agent may typically be a compound in which an oxygen atom in the organic compound is bonded (covalently or coordinately bonded) to the polyvalent metal.
[0100] The content of the crosslinking agent in the adhesive composition is not particularly limited. From the viewpoint of compatibility between cohesiveness and other properties (e.g., adhesive strength), the amount of the crosslinking agent is suitably about 0.005 parts by weight or more, preferably about 0.01 parts by weight or more, more preferably about 0.05 parts by weight or more (e.g., about 0.1 parts by weight or more), and suitably about 10 parts by weight or less, and from the viewpoint of adhesion to the adherend, preferably about 5 parts by weight or less, more preferably about 2 parts by weight or less, even more preferably about 1 part by weight or less, and particularly preferably about 0.5 parts by weight or less.
[0101] In an embodiment in which an isocyanate-based crosslinking agent is used as a crosslinking agent, the amount of the isocyanate-based crosslinking agent in the adhesive composition is suitably about 10 parts by weight or less relative to 100 parts by weight of the polymer (preferably an acrylic polymer) contained in the adhesive composition, and from the viewpoint of fully exerting the adhesive strength to the adherend, it is preferably less than 3 parts by weight, more preferably less than 1 part by weight, even more preferably less than 0.5 parts by weight, and particularly preferably about 0.4 parts by weight or less (for example, about 0.3 parts by weight or less, typically about 0.2 parts by weight or less). The lower limit of the amount of the isocyanate-based crosslinking agent in the adhesive composition is not particularly limited, and it is suitably about 0.005 parts by weight or more relative to 100 parts by weight of the polymer (preferably an acrylic polymer) contained in the adhesive composition, and from the viewpoint of obtaining good cohesive strength, it is preferably about 0.01 parts by weight or more, more preferably about 0.05 parts by weight or more (for example, about 0.1 parts by weight or more).
[0102] (Radical scavenger) The adhesive layer disclosed herein may contain a radical scavenger such as an antioxidant from the viewpoint of storage stability. The radical scavenger is an agent that literally exhibits the function of capturing radicals in the adhesive layer, and therefore can inhibit the addition of radicals to carbon-carbon double bonds present in the adhesive layer before the curing treatment.
[0103] The concept of radical scavengers disclosed herein may include antiaging agents and light stabilizers, a typical example of which is antioxidants. Examples of the antioxidants include various conventionally known antioxidants such as phenol-based antioxidants, phosphorus-based (phosphite-based) antioxidants, sulfur-based antioxidants, and amine-based antioxidants. The antioxidants may be used alone or in combination of two or more.
[0104] Examples of the phenol-based antioxidants include monophenol-based antioxidants such as 2,6-di-t-butyl-4-methylphenol and 2,6-di-tert-butyl-4-ethylphenol; 2,2'-methylenebis(4-methyl-6-t-butylphenol), 2,2'-methylenebis(4-ethyl-6-t-butylphenol), 4,4'-butylidenebis(3-methyl-6-t-butylphenol), 4,4'-thiobis(3-methyl-6-t-butylphenol), and the like. bisphenol-based antioxidants such as 1,3,5-trimethyl-2,4,6-tris(3,5-di-t-butyl-4-hydroxybenzyl)benzene, tetrakis-[methylene-3-(3',5'-di-t-butyl-4'-hydroxyphenyl)propionate]methane, and 1,1,3-tris(2-methyl-4-hydroxy-5-t-butylphenyl)butane.
[0105] The phenol-based antioxidant may be a hindered phenol-based antioxidant. Examples of the hindered phenol-based antioxidant include pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 4,6-bis(dodecylthiomethyl)-o-cresol, triethylene glycol-bis[3-(3-tert-butyl-5-methyl-4-hydroxyphenyl)propionate, bis(2,2,6,6-tetramethyl-4-piperidyl)sebacate, and polycondensates of dimethyl succinate and 4-hydroxy-2,2,6,6-tetramethyl-1-piperidineethanol (dimethyl succinate-1-(2-hydroxyethyl)-4-hydroxy-2,2,6,6-tetramethylpiperidine polycondensates).
[0106] Examples of phosphorus-based antioxidants include tris(2,4-di-t-butylphenyl)phosphite, tris(nonylphenyl)phosphite, triphenyl phosphite, and distearyl pentaerythritol diphosphite. Examples of the sulfur-based antioxidant include dilauryl-3,3'-thiodipropionate, dimyristyl-3,3'-thiodipropionate, distearyl-3,3'-thiodipropionate, pentaerythritol tetralauryl thiopropionate, and the like. Examples of the amine-based antioxidant include phenyl-α-naphthylamine, diphenylamine, and the like.
[0107] The technology disclosed herein may be implemented in an embodiment in which a carbon-carbon double bond is present in the adhesive layer. The adhesive layer may also be implemented in an embodiment in which the adhesive layer contains a radical generator. In this embodiment, it is preferable to limit the amount of radical scavenger in the adhesive layer from the viewpoint of effectively realizing a decrease in adhesive strength during curing treatment. The content of the radical scavenger (typically an antioxidant) in the adhesive layer is appropriately about 3 wt% or less, preferably about 1 wt% or less, more preferably about 0.5 wt% or less, and even more preferably about 0.3 wt% or less (typically 0.1 wt% or less). The adhesive layer may not contain a radical scavenger (typically an antioxidant). However, if no radical scavenger such as an antioxidant is present, oxidation may progress at room temperature due to dissolved oxygen in the adhesive layer, so it is preferable to contain an appropriate amount of radical scavenger (typically an antioxidant). From this viewpoint, it is preferable that the content of the radical scavenger in the adhesive layer is 0.001 wt% or more (for example, 0.005 wt% or more, typically 0.01 wt% or more).
[0108] (Other added ingredients) The pressure-sensitive adhesive composition may contain a tackifier or a silane coupling agent. In the technology disclosed herein, from the viewpoint of peelability after curing treatment, it is appropriate to set the content of the tackifier in the pressure-sensitive adhesive layer to less than 10% by weight (for example, less than about 3% by weight, or even less than 1% by weight), and the pressure-sensitive adhesive layer may be preferably implemented in an embodiment that does not substantially contain a tackifier. The silane coupling agent may be added for the purpose of improving adhesion to an adherend (typically glass), etc.
[0109] In addition, the pressure-sensitive adhesive composition may contain, as necessary, various additives that are common in the field of pressure-sensitive adhesive compositions, such as leveling agents, crosslinking assistants, plasticizers, softeners, fillers, colorants (pigments, dyes, etc.), antistatic agents, ultraviolet absorbers, light stabilizers, etc. As for these various additives, conventionally known ones can be used in the usual manner, and they do not particularly characterize the present invention, so detailed explanations will be omitted.
[0110] In some preferred embodiments, the pressure-sensitive adhesive composition may have a composition in which the content of the polymer (typically a base polymer) is about 90% by weight or more of the total weight of the pressure-sensitive adhesive (solid content of the pressure-sensitive adhesive composition) (i.e., the weight of the pressure-sensitive adhesive layer composed of this pressure-sensitive adhesive). This can preferably achieve a reduction in adhesive strength by curing treatment. From this viewpoint, the content of the polymer is preferably about 95% by weight or more of the total weight of the pressure-sensitive adhesive layer, more preferably about 97% by weight or more, even more preferably about 98% by weight or more, and may be about 99% by weight or more (for example, 99 to 100% by weight). In other words, the content of components other than the polymer (additives, etc.) in the solid content (pressure-sensitive adhesive layer) of the pressure-sensitive adhesive composition is suitably about 10% by weight or less, preferably about 5% by weight or less, more preferably about 3% by weight or less, even more preferably about 2% by weight or less, and may be about 1% by weight or less.
[0111] (Method of forming pressure-sensitive adhesive layer) The adhesive layer disclosed herein may be an adhesive layer formed from an aqueous adhesive composition, a solvent-based adhesive composition, a hot melt-type adhesive composition, or an active energy ray curable adhesive composition. The aqueous adhesive composition refers to an adhesive composition in a form containing an adhesive in a solvent (aqueous solvent) mainly composed of water, and the concept of the aqueous adhesive composition here may include those called water-dispersed adhesive compositions (compositions in which an adhesive is dispersed in water), water-soluble adhesive compositions (compositions in which an adhesive is dissolved in water), and the like. The solvent-based adhesive composition refers to an adhesive composition in a form containing an adhesive in an organic solvent. The technology disclosed herein may be preferably implemented in an embodiment having an adhesive layer formed from a solvent-based adhesive composition.
[0112] The adhesive layer disclosed herein can be formed by a conventionally known method. For example, a method of forming an adhesive layer by applying (typically applying) an adhesive composition to a surface (release surface) having releasability and drying the adhesive composition can be preferably adopted. In addition, a method of forming an adhesive layer by directly applying an adhesive composition to a substrate and drying the substrate (direct method) can also be preferably adopted. Furthermore, a method of forming an adhesive layer on a release surface by applying an adhesive composition to the release surface and drying the adhesive composition, and transferring the adhesive layer to a substrate (transfer method) may be adopted. The release surface may be the surface of a release liner, the back surface of a substrate that has been subjected to a release treatment, or the like. The coating may be performed using a known or commonly used coater such as a gravure roll coater or a reverse roll coater.
[0113] From the viewpoint of promoting the crosslinking reaction and improving the production efficiency, the adhesive composition is preferably dried under heating. The drying temperature can be, for example, about 40°C to 150°C, and is usually preferably about 60°C to 130°C. For example, in drying at the above temperature (for example, drying for 5 minutes or less, typically about 3 minutes), the solvent volatilizes, and this is a treatment for the adhesive composition (layer) before the adhesive layer is formed, and is not a curing treatment in the technology disclosed herein. In addition, after drying the adhesive composition, aging may be performed for the purpose of adjusting the component migration in the adhesive layer, progressing the crosslinking reaction, and relaxing distortion that may exist in the substrate or adhesive layer. The aging conditions are not particularly limited, and for example, aging at a temperature of about 25°C to 70°C (typically 40°C to 60°C) for 10 to 120 hours (typically 24 to 48 hours) is appropriate.
[0114] The thickness of the adhesive layer disclosed herein is not particularly limited and can be appropriately selected depending on the purpose. Usually, the thickness of the adhesive layer is about 5 to 200 μm, and from the viewpoint of adhesion, etc., it is preferably about 10 μm or more (e.g., 15 μm or more, typically 25 μm or more), preferably about 150 μm or less, more preferably 100 μm or less, and even more preferably about 80 μm or less (e.g., 60 μm or less, typically 40 μm or less). When the adhesive sheet disclosed herein is a double-sided adhesive sheet having adhesive layers on both sides of a substrate, the thicknesses of the adhesive layers may be the same or different.
[0115] <Base material layer> In the single-sided or double-sided adhesive substrate-attached adhesive sheet, various sheet-like substrates can be used as the substrate (layer) that supports (backs) the adhesive layer. The substrate can be a resin film, paper, cloth, rubber sheet, foam sheet, metal foil, or a composite of these. Examples of the resin film include polyolefin films such as polyethylene (PE), polypropylene (PP), and ethylene-propylene copolymer; polyester films such as polyethylene terephthalate (PET) and polyethylene naphthalate (PEN); vinyl chloride resin films; vinyl acetate resin films; polyamide resin films; fluororesin films; cellophane; and the like. Other examples of the resin film include resin films formed from one or more engineering plastics (which may be super engineering plastics) such as polyphenylene sulfide resins, polysulfone resins, polyethersulfone resins, polyetheretherketone resins, polyarylate resins, polyamideimide resins, and polyimide resins. The use of engineering plastics is preferable from the viewpoint of heat resistance. Examples of paper include Japanese paper, craft paper, glassine paper, fine paper, synthetic paper, topcoated paper, etc. Examples of cloth include woven fabrics and nonwoven fabrics made of various fibrous materials, either alone or in combination. Examples of the fibrous materials include cotton, staple fiber, Manila hemp, pulp, rayon, acetate fiber, polyester fiber, polyvinyl alcohol fiber, polyamide fiber, polyolefin fiber, etc. Examples of rubber sheets include natural rubber sheets and butyl rubber sheets. Examples of foam sheets include foamed polyurethane sheets and foamed polychloroprene rubber sheets. Examples of metal foils include aluminum foil and copper foil.
[0116] In some preferred embodiments, a resin film having a predetermined rigidity (strength) and excellent processability and handling properties is used as the substrate (layer). By using a resin film substrate with high rigidity, when the adherend is thin, it is possible to suitably prevent the adherend from being bent or damaged during transportation, etc. From the same viewpoint, it is preferable to use a polyester film as the resin film substrate. In this specification, the term "resin film" typically refers to a non-porous film, and is a concept that is distinguished from so-called nonwoven fabrics and woven fabrics. The density of the resin film that can be used as the substrate is approximately 0.85 to 1.50 g / cm. 3 (For example, 0.90 g / cm 3 ~1.20g / cm 3 , typically 0.92 g / cm 3 ~1.05g / cm 3 ) degree.
[0117] In addition, the above-mentioned substrate (e.g., a resin film substrate) may contain various additives such as a filler (inorganic filler, organic filler, etc.), an antiaging agent, an antioxidant, an ultraviolet absorber, an antistatic agent, a lubricant, a plasticizer, a colorant (pigment, dye, etc.), etc., as necessary.
[0118] The surface of the above-mentioned substrate layer (e.g., a resin film substrate, a rubber sheet substrate, a foam sheet substrate, etc.) on which the pressure-sensitive adhesive layer is disposed (the pressure-sensitive adhesive layer side surface) may be subjected to a known or conventional surface treatment such as a corona discharge treatment, a plasma treatment, an ultraviolet irradiation treatment, an acid treatment, an alkali treatment, application of a primer, etc. Such a surface treatment may be a treatment for improving the adhesion between the substrate and the pressure-sensitive adhesive layer, in other words, the anchoring property of the pressure-sensitive adhesive layer to the substrate.
[0119] In some preferred embodiments, an undercoat layer is provided on the surface of the substrate layer on the side of the adhesive layer. In other words, an undercoat layer may be disposed between the substrate layer and the adhesive layer. The undercoat layer forming material is not particularly limited, and one or more of urethane (polyisocyanate) resin, polyester resin, acrylic resin, polyamide resin, melamine resin, olefin resin, polystyrene resin, epoxy resin, phenol resin, isocyanurate resin, polyvinyl acetate resin, etc. may be used. When an acrylic adhesive layer is provided on a resin film substrate, a polyester, urethane, or acrylic undercoat layer is preferred, and when an acrylic adhesive layer is provided on a polyester substrate layer such as a PET film, a polyester undercoat layer is particularly preferred. The thickness of the undercoat layer is not particularly limited, and may usually be in the range of about 0.1 μm to 10 μm (for example, 0.1 μm to 3 μm, typically 0.1 μm to 1 μm). The undercoat layer can be formed by using a known or conventional coater such as a gravure roll coater or a reverse roll coater.
[0120] In addition, when the pressure-sensitive adhesive sheet disclosed herein is a one-sided adhesive sheet in which a pressure-sensitive adhesive layer is provided on one side of a base layer, the surface of the base layer on which the pressure-sensitive adhesive layer is not formed (back surface) may be subjected to a release treatment with a release treatment agent (back surface treatment agent). The back surface treatment agent that can be used to form the back surface treatment layer is not particularly limited, and a silicone-based back surface treatment agent, a fluorine-based back surface treatment agent, a long-chain alkyl-based back surface treatment agent, or other known or commonly used treatment agent can be used depending on the purpose or use.
[0121] The thickness of the base layer is not particularly limited and can be appropriately selected depending on the purpose, but can generally be 1 to 800 μm. From the viewpoint of processability, handling, workability, etc., the thickness of the base layer is suitably 2 μm or more (e.g., 3 μm or more, typically 5 μm or more), preferably about 10 μm or more, more preferably about 25 μm or more (e.g., 30 μm or more), and is suitably about 700 μm or less (e.g., 500 μm or less, typically 200 μm or less), preferably about 100 μm or less, more preferably about 80 μm or less (e.g., about 70 μm or less).
[0122] <Release liner> The release liner can be any conventional release paper, and is not particularly limited. For example, a release liner having a release treatment layer on the surface of a liner substrate such as a resin film or paper, or a release liner made of a low-adhesion material such as a fluorine-based polymer (polytetrafluoroethylene, etc.) or a polyolefin resin (polyethylene, polypropylene, etc.) can be used. The release treatment layer can be formed by surface-treating the liner substrate with a release treatment agent such as a silicone-based, long-chain alkyl-based, fluorine-based, or molybdenum sulfide.
[0123] The total thickness of the adhesive sheet disclosed herein (which may include an adhesive layer and a base layer, but does not include a release liner) is not particularly limited, and is suitably in the range of approximately 5 to 1000 μm. Taking into consideration the adhesive properties and the like, the total thickness of the adhesive sheet is preferably about 10 to 500 μm (e.g., 15 to 300 μm, typically 20 to 200 μm). From the standpoint of handleability and the like, the total thickness of the adhesive sheet is more preferably 30 μm or more (e.g., 50 μm or more, typically 70 μm or more).
[0124] <Application> The use of the pressure-sensitive adhesive sheet disclosed herein is not particularly limited, and it can be preferably used in applications in which it is attached to an adherend and then peeled off, utilizing its ability to be easily separated from the adherend after curing treatment and to prevent adhesive residue when separated from the adherend. Such applications include temporary fixing sheets and protective sheets. For example, it can be preferably used as a process material that is fixed to an adherend and peeled off in the manufacturing process of electronic devices and electronic parts.
[0125] The adhesive sheet disclosed herein may be preferably used as an adhesive sheet used in an environment exposed to heating at a predetermined temperature or higher (for example, 100°C to 230°C, typically 130°C to 200°C, further 150°C to 175°C) after application. Even when used in an environment exposed to heating as described above, the adhesive sheet disclosed herein can adhere well to the adherend with a predetermined or higher adhesive strength before curing treatment, and can be well separated from the adherend after curing treatment, and can prevent adhesive residue when separated from the adherend. The adhesive sheet disclosed herein may also have excellent removability, and is therefore suitable as an adhesive sheet used in an embodiment to be peeled off after the heating.
[0126] Suitable applications of the adhesive sheet disclosed herein include semiconductor element manufacturing applications. For example, in semiconductor wafer processing (typically silicon wafer processing), the adhesive sheet can be preferably used as a wafer fixing sheet (typically a sheet for laser dicing) for fixing the wafer to a fixing plate (e.g., a hard substrate such as a glass plate or an acrylic plate). The adhesive sheet disclosed herein can also be preferably used as a protective sheet for protecting the wafer (e.g., a circuit formation surface) in the above-mentioned wafer processing. The above-mentioned sheet may be required to have a moderate degree of adhesion to the extent that it does not peel off from the adherend (typically a semiconductor element or a hard substrate) during processing or transportation in the above-mentioned manufacturing, and a property of being well peeled off from the adherend after the purpose is achieved. In particular, it is important that the above-mentioned sheet is suppressed from deteriorating in properties such as adhesion due to heating during the manufacturing of semiconductor elements. The adhesive sheet disclosed herein can be preferably used as one that can satisfy the performance required for the above-mentioned applications.
[0127] In addition, the adhesive sheet disclosed herein may be preferably used for, for example, fixing a plurality of miniaturized semiconductor chips (such as LED chips) on the adhesive surface of a single adhesive sheet, sealing the semiconductor chips with resin on the adhesive sheet, and separating the semiconductor chips from the adhesive sheet after the processing is completed. In this mode of use, high temperature heating is performed during resin sealing, and heat resistance is required that does not impair easy peeling even after heating. The adhesive sheet disclosed herein maintains good characteristics (for example, adhesion) against the above-mentioned heating, prevents adhesive residue when peeled off from the adherend (semiconductor chip), and can also have excellent peelability from the adherend. The adhesive sheet disclosed herein can prevent damage to the adherend surface during peeling. More specifically, it can not only be peeled off well from the semiconductor chip, but also have excellent peelability from the sealing resin. The pressure-sensitive adhesive sheet is suitable as a pressure-sensitive adhesive sheet used in FOWLP (Fan Out Wafer Level Package) and CSP (Chip Scale Package), and by using it for the above applications, it can contribute to increasing the capacity and performance of various semiconductor products.
[0128] As described above, the adhesive sheet disclosed herein is preferably applied to the manufacturing application of semiconductor elements. Therefore, according to this specification, a manufacturing method of a semiconductor element using the adhesive sheet disclosed herein is provided. In some preferred embodiments, this manufacturing method includes a step of fixing a semiconductor to the adhesive sheet (fixing step); and a step of processing the semiconductor (processing step). In a more preferred embodiment, the processing step includes a step of heating the adhesive sheet and the semiconductor to 100°C or higher (e.g., 150°C to 175°C) (heating step). The processing step may include a dicing step before or after the heating step. The semiconductor may be in the form of a semiconductor wafer or a semiconductor chip. The heating step may be, for example, a step of sealing the semiconductor chip with a resin (e.g., silicone resin, etc.).
[0129] The above manufacturing method may also include a step (removal step, typically a peeling step) of separating the adhesive sheet from the semiconductor (typically a semiconductor chip) after the processing step. The separation may be performed by attaching a transfer tape to the surface of the semiconductor (the surface opposite to the adhesive surface of the adhesive sheet). In the above manufacturing method, typically, after the processing step and before the separation step, a curing treatment is performed on the adhesive sheet. The curing treatment may preferably be an active energy ray (e.g., UV) irradiation step. Note that other technical matters necessary for the production of semiconductor elements will not be described here in particular, since they can be performed by a person skilled in the art based on the technical common sense in the field.
[0130] In addition, the adhesive sheet disclosed herein is suitable as a temporary fixing sheet used in the manufacture of thin substrates such as circuit boards (e.g., printed wiring boards (PCBs) and flexible circuit boards (FPCs)), organic EL panels, color filters, electronic paper, and flexible displays. For example, in the fixing of chips on a PCB, heating may be involved in wire bonding or resin sealing, so that the adhesive sheet disclosed herein is used to fix an adherend, and a curing treatment is performed after heating, thereby preventing adhesive residue when separated from the adherend and allowing the adhesive sheet to be satisfactorily separated from the adherend with little load on the adherend. Furthermore, the adhesive sheet disclosed herein can be preferably used as a support tape for a thin wafer. In this application, in printing solder paste on a thin wafer, the adhesive sheet may be exposed to heating in a solder reflow process. The adhesive sheet disclosed herein is attached to a thin wafer as an adherend, used as a support tape, and then heated and cured at an appropriate timing, thereby preventing adhesive residue when separated from the adherend and allowing the adhesive sheet to be satisfactorily separated from the adherend.
[0131] As described above, the adhesive sheet disclosed herein is preferably applied to the production of thin substrates such as circuit boards (typically PCBs). Thus, according to this specification, a method for producing a thin substrate (e.g., a circuit board, an organic EL panel, a color filter, electronic paper, a flexible display) using the adhesive sheet is provided. In some preferred embodiments, the production method includes a step of fixing a thin substrate (typically the back surface of the substrate) to the adhesive sheet (fixing step); and a step of processing the thin substrate. In a further preferred embodiment, the processing step includes a step of heating to 60°C or higher (e.g., 100°C to 230°C, typically 150°C to 175°C) (heating step).
[0132] The processing step according to some embodiments includes a die bonding step and a wire bonding step, and may further include a molding step and a package dicing step. The die bonding step is typically a step of arranging a plurality of chips on a thin substrate such as a PCB, the wire bonding step is a step of bonding wires to the chips, and the molding step may be, for example, a step of sealing the chips on the PCB with a resin such as an epoxy resin. The manufacturing method may also include a step of separating the adhesive sheet from the thin substrate after the processing step (a removal step, typically a peeling step). The manufacturing method typically includes a curing process for the adhesive sheet after the processing step and before the separation step. The curing process may preferably be a step of irradiating with active energy rays (e.g., UV). In the step of separating the adhesive sheet from the thin substrate, the adhesive sheet is separated and removed from the chips arranged on the adhesive sheet and the sealing resin (resin cured product) after heating during the curing of the sealing resin, etc. Note that other technical matters necessary for the manufacturing of a thin substrate such as a PCB will not be described here, since they can be implemented by a person skilled in the art based on the technical common sense of the field.
[0133] A method for producing a circuit board (typically, FPC: Flexible Print Circuit) according to some other embodiments includes a step of bonding the adhesive sheet disclosed herein as a support tape to the back surface of a fixing tape to which a thin wafer is fixed; and a step of processing the thin wafer. In a more preferred embodiment, the processing step includes a step (heating step) of heating to 100°C or higher (for example, 150°C to 300°C, typically 250°C to 260°C). The processing step in such a production method may be a solder paste printing step. The solder paste printing step may include a solder ball drop step or a solder reflow step. The production method may include a step (removal step, typically a peeling step) of separating the adhesive sheet and the fixing tape after the processing step. In the production method, typically, a curing treatment is performed on the adhesive sheet after the processing step and before the separation step. The curing treatment may preferably be an active energy ray (for example, UV) irradiation step. Other technical matters required for manufacturing thin substrates such as FPCs will not be described here, as they can be implemented by a person skilled in the art based on the common technical knowledge in the field.
[0134] The matters disclosed in this specification include the following. [1] A pressure-sensitive adhesive sheet having a pressure-sensitive adhesive layer, The glass transition temperature of the polymer contained in the pressure-sensitive adhesive layer is −63° C. or higher; An adhesive sheet having an adhesive strength reduction rate calculated by the following formula of 17% or more. Adhesive force reduction rate (%)=(1-B / A)×100 (In the formula, A is the initial 180-degree peel strength ([N / 20 mm]) against a stainless steel plate, and B is the initial peel strength ([N / 20 mm]) against a stainless steel plate after bonding to the plate, heating at 180°C for 1 hour, and leaving at 25°C for 30 minutes at an illuminance of 60 mW / cm 2 The 180 degree peel strength ([N / 20mm]) after heat-hardening treatment on a stainless steel plate measured after exposure to ultraviolet light at 1000 K. [2] The pressure-sensitive adhesive sheet described in [1] above, having an initial 180 degree peel strength against a stainless steel plate of greater than 1.0 N / 20 mm. [3] Characteristics: After heating at 180°C for 1 hour and leaving at 25°C for 30 minutes, the illuminance is 60mW / cm 2 The pressure-sensitive adhesive sheet according to the above-mentioned [1] or [2], wherein after a heat-curing treatment in which ultraviolet light is irradiated at RT, the pressure-sensitive adhesive layer has an elastic modulus of 22 MPa or more as measured by a nanoindentation method. [4] The pressure-sensitive adhesive sheet according to any one of the above [1] to [3], wherein the pressure-sensitive adhesive layer contains a carbon-carbon double bond. [5] The pressure-sensitive adhesive sheet according to any one of the above [1] to [4], wherein the polymer includes a polymer having a carbon-carbon double bond. [6] The pressure-sensitive adhesive sheet according to any one of the above [1] to [5], wherein the polymer is an acrylic polymer. [7] The acrylic polymer is a polymer of a monomer component containing an alkyl (meth)acrylate, The pressure-sensitive adhesive sheet according to the above-mentioned [6], wherein the alkyl (meth)acrylate includes an alkyl (meth)acrylate A1 having an alkyl group with 9 or less carbon atoms. [8] The pressure-sensitive adhesive sheet according to the above [7], wherein the alkyl(meth)acrylate A1 includes an alkyl(meth)acrylate having an alkyl group with 7 or less carbon atoms. [9] The pressure-sensitive adhesive sheet according to the above-mentioned [7] or [8], wherein the content of the alkyl (meth)acrylate A1 in the monomer components is 20% by weight or more.
[10] The pressure-sensitive adhesive sheet according to any one of the above [7] to [9], wherein the alkyl (meth)acrylate contains an alkyl (meth)acrylate A2 having an alkyl group with 7 or more carbon atoms as the alkyl (meth)acrylate A1 or as a monomer different from the alkyl (meth)acrylate A1.
[11] The pressure-sensitive adhesive sheet according to any one of the above [1] to
[10] , further comprising a base layer, the pressure-sensitive adhesive layer being provided on at least one surface of the base layer.
[12] The pressure-sensitive adhesive sheet according to the above-mentioned
[11] , which is a single-sided pressure-sensitive adhesive sheet having the pressure-sensitive adhesive layer provided on one surface of the base layer.
[13] The pressure-sensitive adhesive sheet according to the above-mentioned
[11] , which is a double-sided pressure-sensitive adhesive sheet in which the pressure-sensitive adhesive layers are provided on both sides of the base layer.
[14] The pressure-sensitive adhesive sheet according to the above-mentioned
[11] , which is a double-sided pressure-sensitive adhesive sheet having a first pressure-sensitive adhesive layer provided as the pressure-sensitive adhesive layer on one surface of the base layer, and a second pressure-sensitive adhesive layer different from the first pressure-sensitive adhesive layer provided on the other surface of the base layer.
[15] The pressure-sensitive adhesive sheet according to any one of the above [1] to
[10] , which is a substrateless double-sided pressure-sensitive adhesive sheet substantially composed of the pressure-sensitive adhesive layer.
[0135] Some examples of the present invention will be described below, but it is not intended that the present invention be limited to those shown in these examples. In the following description, "parts" and "%" are by weight unless otherwise specified.
[0136] <Evaluation method> [Elastic modulus of adhesive layer after heat-curing treatment] The elastic modulus of the adhesive layer after the heat-curing treatment is measured based on the nanoindentation method. The elastic modulus based on the nanoindentation method refers to the elastic modulus obtained from the applied load-indentation depth curve obtained by continuously measuring the load and indentation depth when an indenter is pressed into a sample (adhesive layer surface) during loading and unloading. The heat-curing treatment conditions and the measurement conditions for the nanoindentation method are as follows.
[0137] (Heat-curing treatment conditions) Heat treatment: 180℃, 1 hour Cooling: Room temperature (25℃) environment, 30 minutes UV irradiation: After heat treatment and cooling, carry out under the following conditions. UV irradiation equipment: NEL SYSTEM UM810 manufactured by Nitto Seiki Co., Ltd., high pressure mercury lamp light source Irradiation amount: illuminance 60mW / cm 2 , time 8 seconds
[0138] (Measuring conditions for nanoindentation method) Nanoindenter: "Triboindenter" manufactured by Hysitron Indenter used: Berkovich (triangular pyramid) type diamond indenter Measurement method: Single indentation measurement Measurement temperature: room temperature (25℃) Indentation depth setting: 3000nm Push-pull speed: 500 nm / sec
[0139] [Initial adhesive strength] The adhesive sheet is cut to a size of 20 mm wide and 140 mm long to prepare a measurement sample, which is then bonded to a stainless steel plate (SUS304BA plate) in accordance with JIS Z 0237:2000. Specifically, in an atmosphere of 23±2°C temperature and 65±5%RH humidity, the measurement sample is pressed and bonded to the SUS304BA plate by rolling a 2 kg roller back and forth once. Then, the measurement sample is set in a tensile tester with a thermostatic chamber set at 23°C and left for 30 minutes. After leaving the sample, the load is measured when the measurement sample is peeled off from the stainless steel plate under conditions of a peel angle of 180° and a speed of 300 mm / min in an environment of 23°C, and the uneven average load at that time is calculated, and this is defined as the initial adhesive strength (initial 180° peel strength against SUS plate) [N / 20 mm width]. As the tensile tester, the product name "Shimadzu Autograph AG-120kN" manufactured by Shimadzu Corporation or an equivalent product can be used. Furthermore, when the measurement sample is a double-sided pressure-sensitive adhesive sheet, the measurement can be performed with the non-measurement side backed with a PET film.
[0140] [Adhesive strength after heat-curing treatment] The adhesive sheet is cut to a size of 20 mm wide and 140 mm long to prepare a measurement sample, which is then bonded to a stainless steel plate (SUS304BA plate) in accordance with JIS Z 0237:2000. Specifically, in an atmosphere of 23±2°C temperature and 65±5%RH humidity, the measurement sample is pressed and bonded to the SUS304BA plate by rolling a 2 kg roller back and forth once. After bonding, the measurement sample is heated at 180°C for 1 hour. After heating, it is allowed to cool for 30 minutes in a room temperature (25°C) environment. After cooling, UV is irradiated from the base layer side of the adhesive sheet (the side opposite the adhesive surface to be measured, also called the back side) under the following conditions. After UV irradiation, the sample is set in a thermostatically-controlled tensile tester set at 23°C and left for 30 minutes. After leaving it, the load when the measurement sample is peeled off from the SUS304BA plate under the conditions of a peel angle of 180° and a speed of 300 mm / min in an environment of 23°C is measured, and the unevenness average load at that time is calculated and this is the adhesive strength after heat-curing treatment (180° peel strength after heat-curing treatment against SUS plate) [N / 20 mm width]. As a tensile tester, Shimadzu Corporation's product name "Shimadzu Autograph AG-120kN" or an equivalent product can be used. In addition, when the measurement sample is a double-sided adhesive sheet, the measurement can be performed by backing the non-measurement side with a PET film. (UV irradiation conditions) UV irradiation equipment: NEL SYSTEM UM810 manufactured by Nitto Seiki Co., Ltd., high pressure mercury lamp light source Irradiation amount: illuminance 60mW / cm 2 , time 8 seconds
[0141] [Adhesive force reduction rate] The adhesive strength reduction rate (%) is calculated from the formula: adhesive strength reduction rate (%) = (1-B / A) x 100. In the above formula, A is the initial adhesive strength, and B is the adhesive strength after the heat-curing treatment.
[0142] [Resin peelability] A resin solution (solid concentration: 23.6%) is prepared by mixing 100 parts of a naphthalene-type bifunctional epoxy resin (manufactured by DIC Corporation, product name "HP4032D", epoxy equivalent: 144), 40 parts of a phenoxy resin (manufactured by Mitsui Chemicals, Inc., product name "EP4250"), 129 parts of a phenolic resin (manufactured by Meiwa Chemical Industry Co., Ltd., product name "MEH-8000"), 1137 parts of spherical silica (manufactured by Admatechs Co., Ltd., product name "SO-25R"), 14 parts of a dye (manufactured by Orient Chemical Industry Co., Ltd., product name "OIL BLACK BS"), 1 part of a curing catalyst (manufactured by Shikoku Chemical Industry Co., Ltd., product name "2PHZ-PW"), and 30 parts of methyl ethyl ketone. The resin solution is applied onto the adhesive layer of the adhesive sheet, and the resin solution is heated at 170°C for 10 minutes to harden it, forming a resin cured product (cured sealing resin) on the adhesive layer. The resin solution is applied to a coating size of 3 cm x 3 cm and a thickness of 1 mm. After cooling, the adhesive sheet is peeled off from the resin cured product under certain conditions, and the peelability at that time is evaluated according to the following criteria. ◯: The cured resin can be peeled off without cracking, chipping or breaking. ×: The cured resin cracks, chips or breaks upon peeling.
[0143] [Workpiece retention] Based on the above initial adhesive strength measurement results, the following criteria are used for evaluation. ◎: 4.0N / 20mm or more ○: Over 1.0N / 20mm and under 4.0N / 20mm ×: 1.0N / 20mm or less
[0144] [Adhesive residue evaluation] A strip of PET tape (5 μm thick) having a specified width is attached to a stainless steel plate (SUS304BA plate) to form a step on the flat surface of the SUS plate. An adhesive sheet is cut into a strip of a specified width, and the adhesive sheet is attached to the SUS plate from above the PET tape, including the step caused by the PET tape, so that the longitudinal direction of the adhesive sheet is perpendicular to the longitudinal direction of the strip of PET tape. The pressure bonding by attachment is performed by moving a 2 kg roller back and forth once. Then, heating and UV irradiation are performed under the same conditions as the heating, UV irradiation, and peeling for the adhesive strength after the heating-curing treatment, and the adhesive sheet is peeled off from the SUS plate with the PET tape. The step part of the adherend after the adhesive sheet is peeled off is observed with a laser microscope (108 times magnification), and the state of adhesive residue is judged according to the following criteria. ⊚: The size of the adhesive component (adhesive residue) remaining on the adherend was less than 10 μm, or no adhesive residue was observed (interface peeling). ○: Adhesive residue of 10 μm or more and less than 100 μm in size was observed. Slight cohesive failure was observed. ×: Adhesive residue of 100 μm or more in size was observed (cohesive failure).
[0145] <Example 1> A monomer mixture was prepared in a reaction vessel equipped with a thermometer, a stirrer, a nitrogen inlet tube, etc., with a blending ratio of 65 parts of ethyl acrylate (EA), 17 parts of lauryl acrylate (LA), and 18 parts of 2-hydroxyethyl acrylate (HEA). 0.225 parts of BPO (trade name "Niper BW" manufactured by NOF Corp.) as a polymerization initiator in terms of solid content and ethyl acetate as a polymerization solvent were added to 100 parts of this monomer mixture, and a polymerization reaction was carried out at about 60°C under a nitrogen gas stream, resulting in an ethyl acetate solution of about 30% acrylic polymer. 23 parts of methacryloyloxyethyl isocyanate (MOI) were added to this to prepare an acrylic polymer having a carbon-carbon double bond. The Tg of this acrylic polymer was -18.0°C. In addition, to the ethyl acetate solution of the acrylic polymer, 0.2 parts of an isocyanate crosslinking agent (trade name "Coronate L" manufactured by Nippon Polyurethane Industry Co., Ltd.) and 3 parts of a photopolymerization initiator (trade name "Irgacure 127" manufactured by Ciba Specialty Chemicals Co., Ltd.: 2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)-benzyl]phenyl}-2-methyl-propan-1-one) were added in a ratio of 100 parts of the solid content of the acrylic polymer. In addition, an antioxidant (trade name "IRGANOX1010" manufactured by Ciba Japan Co., Ltd.; pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]) was added in a ratio of 0.1% in the adhesive layer. In this way, the adhesive composition according to this example was obtained. The above adhesive composition was applied onto an easy-adhesion treated PET film, dried at 120°C for 3 minutes, and then aged at 50°C for 24 hours to produce a single-sided adhesive sheet having a 30 μm thick adhesive layer on one side of a 50 μm thick PET resin substrate layer.
[0146] <Examples 2 to 14 and 16> A pressure-sensitive adhesive composition according to each example was prepared in the same manner as in Example 1, except that the monomer composition of the acrylic polymer was changed to that shown in Table 1, and a single-sided pressure-sensitive adhesive sheet according to each example was produced using the obtained pressure-sensitive adhesive composition in the same manner as in Example 1. In Table 1, 2EHA is 2-ethylhexyl acrylate, BA is n-butyl acrylate, and ACMO is N-acryloylmorpholine.
[0147] <Example 15> The adhesive composition of this example was prepared in the same manner as in Example 14, except that the amount of isocyanate-based crosslinking agent used was changed to 1.0 part, and the single-sided adhesive sheet of this example was produced in the same manner as in Example 14 using the obtained adhesive composition.
[0148] The pressure-sensitive adhesive sheets according to the examples were evaluated according to the evaluation methods described above. The results are shown in Table 1. Table 1 also shows an overview of each example (composition and polymer Tg).
[0149] [Table 1]
[0150] As shown in Table 1, the adhesive sheets according to Examples 1 to 13, in which the Tg of the polymer contained in the adhesive layer was -63°C or higher and the adhesive strength reduction rate was 17% or higher, could be easily separated (peeled) from the adherend in the resin peelability evaluation. Furthermore, the adhesive sheets of Examples 1 to 13 were attached to an adherend having a step, heated at a high temperature of 180°C, cured, and then peeled from the adherend in an adhesive residue evaluation test, and were unlikely to leave adhesive residue. Furthermore, the adhesive sheets of Examples 1 to 13 had an initial adhesive strength of more than 1.0 N / 20 mm before the heating-curing treatment, and had good results in work retention. On the other hand, Examples 14 to 15, in which an adhesive layer containing a polymer with a Tg lower than -63°C was used, all had poor results in the adhesive residue evaluation test. Furthermore, Example 16, in which the adhesive strength reduction rate was less than 17%, had poor results in the resin peelability evaluation test, and also could not be peeled from the adherend in the adhesive residue evaluation (not peelable). The above results show that an adhesive sheet in which the glass transition temperature of the polymer contained in the adhesive layer is -63°C or higher and the adhesive strength reduction rate is 17% or higher can be easily separated from the adherend after curing treatment, and adhesive residue can be prevented, even when exposed to high temperatures.
[0151] Although the specific examples of the present invention have been described in detail above, these are merely examples and do not limit the scope of the claims. The technology described in the claims includes various modifications and changes of the specific examples exemplified above. [Explanation of symbols]
[0152] 1,2,3,4,5,6 Adhesive sheet 10 Base material layer 21, 22 Adhesive layer 31,32 Release liner
Claims
1. A pressure-sensitive adhesive sheet having a pressure-sensitive adhesive layer, The pressure-sensitive adhesive layer contains a polymer having a glass transition temperature of −63° C. or higher, the polymer is an acrylic polymer having a carbon-carbon double bond, The acrylic polymer is a polymer of a monomer component including an alkyl (meth)acrylate, The monomer component further includes a hydroxyalkyl (meth)acrylate as a hydroxyl group-containing monomer, The content of the hydroxyl group-containing monomer in the monomer component is 1% by weight or more and 30% by weight or less, the carbon-carbon double bond of the acrylic polymer is introduced by incorporating an isocyanate group-containing monomer having a carbon-carbon double bond into the acrylic polymer; the content of the isocyanate group-containing monomer is 1 part by weight or more and 35 parts by weight or less based on 100 parts by weight of the acrylic polymer before the carbon-carbon double bond is introduced, The alkyl (meth)acrylate contains 35% by weight or more of alkyl (meth)acrylate having an alkyl group with 2 or less carbon atoms based on the total amount of the alkyl (meth)acrylate, The alkyl (meth)acrylate further includes an alkyl (meth)acrylate having an alkyl group having 7 or more carbon atoms, The pressure-sensitive adhesive composition used to form the pressure-sensitive adhesive layer contains an isocyanate-based crosslinking agent, The content of the isocyanate-based crosslinking agent is less than 0.5 parts by weight based on 100 parts by weight of the acrylic polymer, An adhesive sheet having an adhesive strength reduction rate calculated by the following formula of 17% or more. Adhesive strength reduction rate (%) = (1-B / A) x 100 (In the formula, A is the initial 180-degree peel strength ([N / 20 mm]) against a stainless steel plate, and B is the initial peel strength ([N / 20 mm]) against a stainless steel plate after being attached to the plate, heated at 180° C. for 1 hour, and left at 25° C. for 30 minutes, with an illuminance of 60 mW / cm 2 The peel strength is the 180° peel strength ([N / 20 mm]) after heat-hardening treatment on a stainless steel plate, measured after irradiation with ultraviolet light at 1000 K.
2. 2. The pressure-sensitive adhesive sheet according to claim 1, which has an initial 180 degree peel strength from a stainless steel plate of greater than 1.0 N / 20 mm.
3. Characteristics: After heating at 180°C for 1 hour and leaving at 25°C for 30 minutes, the illuminance was 60 mW / cm 2 3. The pressure-sensitive adhesive sheet according to claim 1, wherein after a heat-curing treatment in which the pressure-sensitive adhesive layer is irradiated with ultraviolet light at 400 rpm, the elastic modulus of the pressure-sensitive adhesive layer is 22 MPa or more as measured by a nanoindentation method.
4. The pressure-sensitive adhesive sheet according to any one of claims 1 to 3, further comprising a base layer, the pressure-sensitive adhesive layer being provided on at least one surface of the base layer.
5. The pressure-sensitive adhesive sheet according to claim 4 , which is a single-sided pressure-sensitive adhesive sheet in which the pressure-sensitive adhesive layer is provided on one surface of the base layer.
6. The pressure-sensitive adhesive sheet according to claim 4 , which is a double-sided pressure-sensitive adhesive sheet in which the pressure-sensitive adhesive layers are provided on both sides of the base layer.
7. The pressure-sensitive adhesive sheet according to claim 4, which is a double-sided pressure-sensitive adhesive sheet having a first pressure-sensitive adhesive layer provided on one side of the base layer as the pressure-sensitive adhesive layer, and a second pressure-sensitive adhesive layer different from the first pressure-sensitive adhesive layer provided on the other side of the base layer.
8. The pressure-sensitive adhesive sheet according to any one of claims 1 to 3, which is a substrate-less double-sided pressure-sensitive adhesive sheet substantially composed of only the pressure-sensitive adhesive layer.
Citation Information
Patent Citations
Pressure-sensitive adhesive sheet for semiconductor wafer processing
JP2001200215A
Manufacturing method of semiconductor device
JP2007242698A
Substrateless adhesive sheet for semiconductor wafer protection, semiconductor wafer backside grinding method using the adhesive sheet, and production method of the adhesive sheet
JP2010212474A
Pressure sensitive adhesive sheet
JP2015059179A
Resin sheet
JP2015120884A
